Electrolyte membrane for redox flow battery, redox flow battery and method for producing electrolyte membrane
By controlling the dimensional change rate and crack area rate of the electrolyte membrane in a specific solution, the problems of insufficient barrier properties of the redox flow battery separator and swelling of the electrolyte membrane are solved, and self-discharge suppression and battery performance are achieved.
Patent Information
- Application Number
- CN202080019594.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-09-13
- Filing Date
- 2020-03-06
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2040-03-06
AI Technical Summary
The separator barrier properties of the redox flow battery are insufficient, resulting in the diffusion of active substance ions, reducing battery capacity and current efficiency. At the same time, the perfluorocarbon polymer electrolyte membrane swells when it comes into contact with the electrolyte, affecting battery performance.
By controlling the size change rate of the electrolyte membrane within a specific range in 2M aqueous sulfuric acid solution or distilled water, the crack area ratio is ensured to be less than 1.5%, thereby improving the barrier property and stability of the electrolyte membrane.
It achieves suppression of self-discharge and excellent battery performance, extends the service life of the electrolyte membrane, and improves the durability of the battery.
Smart Images

Figure CN113544886B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to an electrolyte membrane for a redox flow battery, a redox flow battery, and a method for producing the electrolyte membrane. Background Art
[0002] In recent years, renewable energy sources such as solar power generation and wind power generation have been gradually introduced, but the output power of renewable energy sources fluctuates due to weather and time. Therefore, in order to absorb the output power fluctuations and stabilize the power, it is necessary to install large-scale storage batteries.
[0003] As one of the large-capacity storage batteries, the redox flow battery has attracted much attention from the viewpoint of long life and recyclable electrolyte. The redox flow battery has a unit structure in which a diaphragm is provided between the positive electrode and the negative electrode, and charging and discharging are performed by supplying electrolyte to the positive and negative chambers respectively. The electrolyte generally uses metal ions whose valence changes by oxidation and reduction in an acidic solution as active materials. In addition, the diaphragm generally has the function of allowing protons in the electrolyte to pass through and blocking the ions of the active material present in the positive and negative electrode units, and an electrolyte membrane can be used. However, depending on the type and valence of the ions of the active material, the barrier property of the diaphragm is insufficient, and the ions of the active material will diffuse through the diaphragm, resulting in a decrease in battery capacity and a decrease in current efficiency.
[0004] Regarding the active material used in the electrolyte, vanadium ion electrolytes have been developed in the past due to their solubility, reaction speed, and high electromotive force. In the case of vanadium electrolytes, since the pentavalent vanadium present in the electrolyte has a high oxidizing power, a perfluorocarbon polymer electrolyte membrane with strong oxidation resistance is usually used as the diaphragm in contact with the electrolyte.
[0005] For example, Patent Document 1 describes a fluorine-based ion exchange membrane having a membrane thickness of 1 to 500 μm, a puncture strength of 300 g or more, and a heat shrinkage rate in air at 160° C. of 45% or less.
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent Document 1: International Publication No. 2002 / 062879
[0009] Non-patent literature
[0010] Non-patent literature 1: Mendeleev Communications 2016, Vol. 26, P. 117-P. 118 Summary of the invention
[0011] Problem that the invention aims to solve
[0012] Higher performance is expected for redox flow batteries. From the perspective of the diaphragm, it is expected to reduce resistance and improve the permeation ion selectivity of the barrier ion. As a general method to reduce resistance, there is a method of thinning the diaphragm, but this has a trade-off relationship with the permeation ion selectivity, resulting in a problem of increased self-discharge when used as a battery.
[0013] In addition, the commonly used perfluorocarbon polymer electrolyte membrane swells and changes in size when it comes into contact with the electrolyte. Therefore, when the electrolyte membrane is assembled into a redox flow battery in a dry state and filled with the electrolyte, the following problems arise: the electrolyte membrane swells and bends inside the cell, resulting in a decrease in battery performance or cracks in the membrane in some cases.
[0014] Patent Document 1 discloses that the mechanical strength is improved by stretching the electrolyte membrane, and that the membrane exhibits excellent dimensional stability and ion conductivity. However, the above performance is a characteristic in the use environment of the fuel cell, and it does not disclose the performance of swelling in an electrolyte environment in a temperature range close to room temperature, such as in a redox flow battery, the suppression of permeation of active substances in the electrolyte, and the problems caused by swelling during unit assembly.
[0015] Non-Patent Document 1 discloses that the ion permeation of vanadium as an active material is suppressed and the resistance is reduced by adjusting the stretching ratio and heating temperature of the electrolyte membrane, but discloses that the self-discharge when forming a redox flow battery increases due to stretching.
[0016] An object of the present invention is to provide an electrolyte membrane for a redox flow battery, which has suppressed self-discharge and exhibits excellent battery performance, and a method for producing a redox flow battery and an electrolyte membrane.
[0017] Solutions for solving problems
[0018] The inventors of the present invention have conducted in-depth research on methods for solving the above-mentioned problems and found that the above-mentioned problems can be solved by setting the dimensional change rate of the electrolyte membrane caused by immersion in a 2M sulfuric acid aqueous solution, the dimensional change rate of the electrolyte membrane caused by immersion in distilled water, and the area ratio of the region where the visible light transmittance reaches a certain value or below due to the generation of cracks to a specified range, thereby completing the electrolyte membrane of the present invention.
[0019] That is, the present invention is as follows.
[0020] [1] An electrolyte membrane for a redox flow battery, comprising a perfluorocarbon polymer having ion exchange groups,
[0021] The perfluorocarbon polymer has an equivalent mass EW of ion exchange groups of 600 g / eq or more and 2000 g / eq or less,
[0022] The crack area ratio in the electrolyte membrane is 1.5% or less,
[0023] Among the dimensional changes of the electrolyte membrane caused by immersion in a 2M sulfuric acid aqueous solution, the dimensional change in at least one of the X direction and the Y direction is 80% or more and less than 100%.
[0024] <Dimensional change rate caused by immersion in 2M sulfuric acid aqueous solution>
[0025] A test electrolyte membrane having a moisture content of 1% or less was prepared, and the test electrolyte membrane was immersed in a 2M sulfuric acid aqueous solution at 25°C for 30 minutes. The dimensional change rate in the X direction on the surface of the test electrolyte membrane and in the Y direction orthogonal to the X direction was calculated by the following formula.
[0026] Dimension change rate (%) = {(dimension in a specific direction after immersion) / (dimension in a specific direction before immersion)}×100
[0027] [2] An electrolyte membrane for a redox flow battery, comprising a perfluorocarbon polymer having ion exchange groups,
[0028] The perfluorocarbon polymer has an equivalent mass EW of ion exchange groups of 600 g / eq or more and 2000 g / eq or less,
[0029] The crack area ratio in the electrolyte membrane is 1.5% or less,
[0030] Among the dimensional changes of the electrolyte membrane caused by immersion in distilled water, the dimensional change in at least one of the X direction and the Y direction is 80% or more and less than 100%, and the dimensional change in the Z direction is 115% or more.
[0031] <Dimensional change rate caused by distilled water immersion>
[0032] A test electrolyte membrane having a moisture content of less than 1% was prepared, and the test electrolyte membrane was immersed in distilled water at 25° C. for 30 minutes. The dimensional change rates in the X direction, the Y direction orthogonal to the X direction, and the Z direction orthogonal to the X and Y directions on the surface of the test electrolyte membrane were calculated.
[0033] Dimension change rate (%) = {(dimension in a specific direction after immersion) / (dimension in a specific direction before immersion)}×100
[0034] 〔3〕The electrolyte membrane according to 〔1〕 or 〔2〕, wherein the perfluorocarbon polymer contains a structure represented by the following formula (1).
[0035] -[CF2-CX 1 X 2 a -[CF2-CF(-O-(CF2-CF(CF2X 3 )) b -O c -(CFR 1 ) d -(CFR 2 ) e -(CF2) f -X 4 )] g - (1)
[0036] (In formula (1), X 1 , X 2 and X 3 are each independently a halogen atom or a perfluoroalkyl group having 1 to 3 carbon atoms; X 4 is a -COOZ group, -SO3Z group, -PO3Z2 group or -PO3HZ group; Z is a hydrogen atom, an alkali metal atom, an alkaline earth metal atom, NH4, NH3R 11 , NH2R 11 R 12 , NHR 11 R 12 R 13 or NR 11 R 12 R 13 R 14 ; R 11 , R 12 , R 13 and R 14 are each independently an alkyl group or an aryl group; R 1 and R 2 are each independently a halogen atom, a perfluoroalkyl group having 1 to 10 carbon atoms or a fluorochloroalkyl group having 1 to 10 carbon atoms; a and g are numbers satisfying 0 ≤ a < 1, 0 < g ≤ 1 and a + g = 1; b is an integer from 0 to 8; c is 0 or 1; d, e and f are each independently integers from 0 to 6. Among them, d, e and f are not simultaneously 0.)
[0037] 〔4〕The electrolyte membrane according to any one of 〔1〕 to 〔3〕, wherein the perfluorocarbon polymer contains a structure represented by the following formula (2).
[0038] -[CF2CF2] a -[CF2-CF(-O-(CF2) m -SO3H)]g - (2)
[0039] (In formula (2), a and g are numbers satisfying 0 ≤ a < 1 and 0 < g ≤ 1, and a + g = 1; m is an integer from 1 to 6.)
[0040] 〔5〕The electrolyte membrane according to any one of 〔1〕 to 〔4〕, wherein the diameter of ionic clusters in the thickness direction measured by small-angle X-ray scattering in the electrolyte membrane is 3.0 nm or more.
[0041] 〔6〕The electrolyte membrane according to any one of 〔1〕 to 〔5〕, wherein the peak intensity of the crystalline long period measured by small-angle X-ray scattering in the electrolyte membrane is 0.5 or less.
[0042] 〔7〕The electrolyte membrane according to any one of 〔1〕 to 〔6〕, wherein at least one surface of the electrolyte membrane is covered with an anion-exchangeable compound.
[0043] 〔8〕The electrolyte membrane according to 〔7〕, wherein the anion-exchangeable compound has a tertiary amino group or a quaternary ammonium group.
[0044] 〔9〕A redox flow battery comprising an electrolytic cell, the electrolytic cell including: a positive electrode unit chamber including a positive electrode formed of a carbon electrode, a negative electrode unit chamber including a negative electrode formed of a carbon electrode, and an electrolyte membrane as a separator for separating and isolating the positive electrode unit chamber from the negative electrode unit chamber,
[0045] The positive electrode unit chamber includes: a positive electrode electrolyte containing an active material,
[0046] The negative electrode unit chamber includes: a negative electrode electrolyte containing an active material,
[0047] The electrolyte membrane is the electrolyte membrane according to any one of 〔1〕 to 〔8〕.
[0048] 〔10〕The redox flow battery according to 〔9〕, wherein the positive electrode electrolyte and the negative electrode electrolyte contain vanadium ions.
[0049] 〔11〕The redox flow battery according to 〔9〕 or 〔10〕, wherein the carbon electrode has continuous voids,
[0050] The carbon electrode contains fibrous carbon,
[0051] The fibrous carbon has an average fiber diameter of 0.1 to 5.0 μm.
[0052] 〔12〕The redox flow battery according to 〔11〕, wherein the carbon electrode is a three-dimensionally continuous carbon structure.
[0053]
[13] The redox flow battery according to
[11] or
[12] , wherein the carbon electrode is a carbon foam having a linear portion and a bonding portion bonding the linear portions.
[0054]
[14] The redox flow battery according to
[13] , wherein the ratio of the number of linear portions of the carbon foam to the number of bonding portions is 1.2 to 1.7.
[0055]
[15] The redox flow battery according to
[13] or
[14] , wherein in at least a portion of the carbon foam, the density of the bonding portions is 15,000 / mm 3 above.
[0056]
[16] A method for producing an electrolyte membrane for a redox flow battery, comprising:
[0057] a step of stretching a raw material film containing a perfluorocarbon polymer having an ion exchange group,
[0058] The perfluorocarbon polymer has an equivalent mass EW of ion exchange groups of 600 g / eq or more and 2000 g / eq or less,
[0059] The crack area ratio in the electrolyte membrane is 1.5% or less,
[0060] Among the dimensional changes of the electrolyte membrane caused by immersion in a 2M sulfuric acid aqueous solution, the dimensional change in at least one of the X direction and the Y direction is 80% or more and less than 100%.
[0061] <Dimensional change rate caused by immersion in 2M sulfuric acid aqueous solution>
[0062] A test electrolyte membrane having a moisture content of 1% or less was prepared, and the test electrolyte membrane was immersed in a 2M sulfuric acid aqueous solution at 25°C for 30 minutes. The dimensional change rate in the X direction on the surface of the test electrolyte membrane and in the Y direction orthogonal to the X direction was calculated by the following formula.
[0063] Dimension change rate (%) = {(dimension in a specific direction after immersion) / (dimension in a specific direction before immersion)}×100
[0064]
[17] A method for producing an electrolyte membrane for a redox flow battery, comprising:
[0065] A step of stretching a raw material film containing a perfluorocarbon polymer having an ion exchange group under heating,
[0066] The perfluorocarbon polymer has an equivalent mass EW of ion exchange groups of 600 g / eq or more and 2000 g / eq or less,
[0067] The crack area ratio in the electrolyte membrane is 1.5% or less,
[0068] Among the dimensional changes of the electrolyte membrane caused by immersion in distilled water, the dimensional change in at least one of the X direction and the Y direction is 80% or more and less than 100%, and the dimensional change in the Z direction is 115% or more.
[0069] <Dimensional change rate caused by distilled water immersion>
[0070] A test electrolyte membrane having a moisture content of less than 1% was prepared, and the test electrolyte membrane was immersed in distilled water at 25° C. for 30 minutes. The dimensional change rates in the X direction, the Y direction orthogonal to the X direction, and the Z direction orthogonal to the X and Y directions on the surface of the test electrolyte membrane were calculated.
[0071] Dimension change rate (%) = {(dimension in a specific direction after immersion) / (dimension in a specific direction before immersion)}×100
[0072]
[18] The method for producing an electrolyte membrane according to
[16] or
[17] , further comprising:
[0073] After the aforementioned stretching step, a relaxation step is performed during cooling.
[0074]
[19] The method for producing an electrolyte membrane according to
[18] , further comprising:
[0075] After the relaxation step, a step of heat treating the obtained film in a restrained state at a temperature not lower than the glass transition temperature and not higher than 100° C. for 1 minute to 30 minutes.
[0076] Effects of the Invention
[0077] According to the present invention, it is possible to provide an electrolyte membrane for a redox flow battery that suppresses self-discharge and exhibits excellent battery performance, and a method for producing a redox flow battery and an electrolyte membrane. BRIEF DESCRIPTION OF THE DRAWINGS
[0078] Figure 1 An example of a schematic diagram of a redox flow battery obtained by using the redox flow battery electrolyte membrane in the present embodiment is shown.
[0079] Figure 2 is a SEM image of the carbon foam obtained in Example 12.
[0080] Figure 3 This is an X-ray CT analysis image of the carbon foam obtained in Example 12.
[0081] Figure 4 This is an X-ray CT analysis image of the carbon foam obtained in Example 12.
[0082] Figure 5 It is for Figure 3 The X-ray CT analysis image of the carbon foam shown is an image after image processing for line and node detection. DETAILED DESCRIPTION
[0083] Hereinafter, this specific embodiment (hereinafter referred to as “this embodiment”) will be described in detail, but the present invention is not limited to the following description and can be implemented with various modifications within the scope of the gist.
[0084] [Electrolyte membrane for redox flow battery]
[0085] The electrolyte membrane of the present embodiment is an electrolyte membrane for a redox flow battery, and contains a perfluorocarbon polymer having an ion exchange group.
[0086] Furthermore, the perfluorocarbon polymer has an equivalent mass EW of the ion exchange group of 600 g / eq or more and 2000 g / eq or less.
[0087] Furthermore, the crack area ratio in the electrolyte membrane of the present embodiment is 1.5% or less.
[0088] In the first embodiment, among the dimensional changes of the electrolyte membrane caused by immersion in a 2M sulfuric acid aqueous solution, the dimensional change in at least one of the X direction and the Y direction is 80% or more and less than 100%.
[0089] <Dimensional change rate caused by immersion in 2M sulfuric acid aqueous solution>
[0090] A test electrolyte membrane having a moisture content of 1% or less was prepared, and the test electrolyte membrane was immersed in a 2M sulfuric acid aqueous solution at 25°C for 30 minutes. The dimensional change rate in the X direction on the surface of the test electrolyte membrane and in the Y direction orthogonal to the X direction was calculated by the following formula.
[0091] Dimension change rate (%) = {(dimension in a specific direction after immersion) / (dimension in a specific direction before immersion)}×100
[0092] In the second embodiment, among the dimensional changes of the electrolyte membrane due to immersion in distilled water, the dimensional change in at least one of the X direction and the Y direction is 80% or more and less than 100%, and the dimensional change in the Z direction is 115% or more.
[0093] <Dimensional change rate caused by distilled water immersion>
[0094] A test electrolyte membrane having a moisture content of less than 1% was prepared, and the test electrolyte membrane was immersed in distilled water at 25° C. for 30 minutes. The dimensional change rates in the X direction, the Y direction orthogonal to the X direction, and the Z direction orthogonal to the X and Y directions on the surface of the test electrolyte membrane were calculated.
[0095] Dimension change rate (%) = {(dimension in a specific direction after immersion) / (dimension in a specific direction before immersion)}×100
[0096] According to the above configuration, a redox flow battery electrolyte membrane with suppressed self-discharge can be provided. According to the above configuration, from another point of view, the membrane deflection can be further suppressed, and the membrane life can be extended when used as a redox flow battery electrolyte membrane.
[0097] The electrolyte membrane according to the present embodiment has the above-described structure, and thus cracks are unlikely to occur in the electrolyte membrane even after repeated use, and has excellent durability.
[0098] <Perfluorocarbon polymer>
[0099] The electrolyte membrane of the present embodiment includes a perfluorocarbon polymer having ion exchange groups.
[0100] The ion exchange group is not particularly limited, and examples thereof include -COOH group, -SO3H group, -PO3H2 group, or salts thereof. The salt is not particularly limited, and examples thereof include alkali metal salts, alkaline earth metal salts, and amine salts.
[0101] (Equivalent mass EW)
[0102] From the viewpoint of suppressing the permeation of active material ions and improving current efficiency, and from the viewpoint of improving proton conductivity and reducing resistance, the perfluorocarbon polymer has an ion exchange group equivalent weight EW of 600 g / eq or more and 2000 g / eq or less.
[0103] From the viewpoint of suppressing the penetration of active material ions and improving current efficiency, the equivalent mass EW of the perfluorocarbon polymer used in this embodiment is 600 g / eq or more, preferably 700 g / eq or more, more preferably 800 g / eq or more, and further preferably 900 g / eq or more. From the viewpoint of improving proton conductivity and reducing resistance, the equivalent mass EW of the perfluorocarbon polymer used in this embodiment is 2000 g / eq or less, preferably 1700 g / eq or less, more preferably 1500 g / eq or less, and further preferably 1200 g / eq or less.
[0104] It should be noted that the equivalent mass EW refers to the dry mass (g) of the perfluorocarbon polymer per 1 equivalent of ion exchange groups.
[0105] The equivalent weight EW of the perfluorocarbon polymer can be determined by subjecting the perfluorocarbon polymer to salt substitution and back titrating the solution with an alkaline solution.
[0106] The equivalent mass EW can be adjusted by the copolymerization ratio of the fluorine-based monomers as the raw materials of the perfluorocarbon polymer, the selection of the monomer types, and the like.
[0107] The perfluorocarbon polymer preferably includes a structure represented by the following formula (1).
[0108] -[CF2-CX 1 X 2 ] a -[CF2-CF(-O-(CF2-CF(CF2X 3 )) b -O c -(CFR 1 ) d -(CFR 2 ) e -(CF2) f -X 4 )] g - (1)
[0109] X in formula (1) 1 , X 2 , X 3 , R 1 , R 2 and a~g are defined as follows, respectively.
[0110] X 1 , X 2 and X 3 Each is independently a halogen atom or a perfluoroalkyl group having 1 to 3 carbon atoms.
[0111] The halogen atom is not particularly limited, and examples thereof include fluorine, chlorine, bromine, and iodine atoms. The perfluoroalkyl group having 1 to 3 carbon atoms is not particularly limited, and examples thereof include trifluoromethyl, pentafluoroethyl, perfluoro-n-propyl, and perfluoro-isopropyl.
[0112] From the perspective of chemical stability such as resistance to oxidative degradation of polymers, X 1 , X 2 and X 3 Each independently is preferably a fluorine atom or a perfluoroalkyl group having 1 to 3 carbon atoms, and more preferably a fluorine atom.
[0113] X 4It is -COOZ group, -SO3Z group, -PO3Z2 group or -PO3HZ group.
[0114] Z is a hydrogen atom, an alkali metal atom, an alkaline earth metal atom, NH4, NH3R 11 , NH2R 11 R 12 , NHR 11 R 12 R 13 , NR 11 R 12 R 13 R 14 .
[0115] Here, R 11 , R 12 , R 13 and R 14 are each independently an alkyl group or an aryl group. R 11 , R 12 , R 13 and R 14 The alkyl group of is preferably an alkyl group having 1 to 6 carbon atoms, more preferably a methyl group, an ethyl group, a n-propyl group, an isopropyl group, a n-butyl group, a sec-butyl group, an isobutyl group or a n-hexyl group. As the aryl group, there is no particular limitation, and examples thereof include a phenyl group and a naphthyl group.
[0116] It should be noted that when X 4 is -PO3Z2 group, Z may be the same or different. As the above alkali metal atom, there is no particular limitation, and examples thereof include a lithium atom, a sodium atom and a potassium atom. As the alkaline earth metal atom, there is no particular limitation, and examples thereof include a calcium atom and a magnesium atom. As X 4 , from the viewpoint of chemical stability such as oxidation degradation resistance of the polymer, SO3Z is preferred.
[0117] R 1 and R 2 are each independently a halogen atom, a perfluoroalkyl group having 1 to 10 carbon atoms or a fluorochloroalkyl group. Here, as the halogen atom of R 1 and R 2 , there is no particular limitation, and examples thereof include a fluorine atom, a chlorine atom, a bromine atom and an iodine atom. Among these, a fluorine atom is preferred.
[0118] a and g are numbers satisfying 0 ≤ a < 1, 0 < g ≤ 1 and a + g = 1. b is an integer from 0 to 8. c is 0 or 1. d, e and f are each independently an integer from 0 to 6. Among them, d, e and f are not simultaneously 0.
[0119] It should be noted that, [CF2-CX 1 X 2] and [CF2-CF(-O-(CF2-CF(CF2X 3 )) b -O c -(CFR 1 ) d -(CFR 2 ) e -(CF2) f -X 4 The arrangement order of the structural units of the present invention is not particularly limited and may be random or blocky.
[0120] As the perfluorocarbon polymer in the present embodiment, perfluorocarbon sulfonic acid resin (hereinafter also referred to as "PFSA resin") is preferred because the effect of the present embodiment tends to be more significant. The PFSA resin in the present embodiment is a resin in which perfluorocarbon as a side chain is bonded to the main chain containing the PTFE skeleton chain, and one to two or more sulfonic acid groups (some of which may be in the form of salts depending on the situation) are bonded to each side chain.
[0121] The PFSA resin preferably contains a repeating unit represented by -[CF2CF2]- and a repeating unit derived from a compound represented by the following formula (3), (4-1) or (4-2).
[0122] CF2=CF(-O-(CF2CFXO) n -[A]) (3)
[0123] (In formula (3), X is F or a perfluoroalkyl group having 1 to 3 carbon atoms, and n is an integer of 0 to 5. [A] is (CF2) m -SO3H, m represents an integer of 0 to 6. Wherein n and m are not 0 at the same time. )
[0124] CF2=CF-O-(CF2) P -CFX(-O-(CF2) K -SO3H) (4-1)
[0125] CF2=CF-O-(CF2) P -CFX(-(CF2) L -O-(CF2) m -SO3H) (4-2)
[0126] (In formulas (4-1) and (4-2), X is a perfluoroalkyl group having 1 to 3 carbon atoms, P is an integer of 0 to 12, K is an integer of 1 to 5, L is an integer of 1 to 5, and m is an integer of 0 to 6. K and L may be the same or different, and P, K, and L may not be 0 at the same time.)
[0127] In addition, the PFSA resin is more preferably a copolymer containing repeating units represented by -[CF2CF2]- and -[CF2-CF(-O-(CF2CFXO) n -(CF2) m -SO3H)]-(wherein X is F or CF3, n is an integer from 0 to 5, and m is an integer from 0 to 12. Here, n and m are not both 0.) The copolymer contains at least one -[CF2-CF(-O-(CF2CFXO) n -(CF2) m -SO3H)]-(wherein X is CF3, n is 0 or 1, and m is an integer from 0 to 12. Here, n and m are not both 0.) When the PFSA resin is a copolymer having the above structure and having a specified equivalent weight EW, the resulting electrolyte membrane has the following tendency: it has sufficient hydrophilicity and strong resistance to electrolyte active substances such as pentavalent vanadium.
[0128] Furthermore, the PFSA resin contains the aforementioned -[CF2-CF(-O-(CF2CFXO) n -(CF2) m -SO3H)]-(wherein n is 0 and m is an integer from 1 to 6), or -[CF2-CF(-O-(CF2) P -CFX(-O-(CF2) K -SO3H))]- and -[CF2-CFX(-O-(CF2) P -CFX(-(CF2) L -O-(CF2) m -SO3H))]- derived from the compound represented by formula (4-1) and the compound represented by formula (4-2) respectively. When there are these two repeating units, there is a tendency for the equivalent weight (EW) to become lower and the hydrophilicity of the resulting electrolyte membrane to become higher.
[0129] The perfluorocarbon polymer represented by formula (1) in this embodiment is more preferably a structure represented by the following formula (2) because there is a tendency for the effects of this embodiment to be more significant.
[0130] -[CF2CF2] a -[CF2-CF(-O-(CF2) m -SO3H)] g - (2)
[0131] In formula (2), a and g are numbers satisfying 0 ≤ a < 1 and 0 < g ≤ 1, and a + g = 1, and m is an integer from 1 to 6.
[0132] The perfluorocarbon polymer in the present embodiment is not particularly limited as long as it has the structure represented by formula (1) or formula (2), and may include other structures.
[0133] From the viewpoint of controlling solubility or swelling, the perfluorocarbon polymer in the present embodiment can directly or indirectly cause a partial crosslinking reaction between molecules by means of ion exchange groups. By performing partial crosslinking, for example, even if the equivalent mass EW of the perfluorocarbon polymer is about 500 g / eq, the water solubility of the perfluorocarbon polymer can be reduced (water resistance is improved).
[0134] In addition, when the perfluorocarbon polymer has a low melt flow value (has a high molecular weight), the aforementioned partial crosslinking can also increase the entanglement between molecules, thereby reducing solubility and excessive swelling.
[0135] As the aforementioned partial cross-linking reaction, for example, there can be listed reactions between ion exchange groups and functional groups or main chains of other molecules; or reactions between ion exchange groups; cross-linking reactions (covalent bonds) with oxidation-resistant low molecular weight compounds, oligomers or polymers, etc., and depending on the circumstances, reactions with salts (including ionic bonds with -SO3H groups) to form substances. As oxidation-resistant low molecular weight compounds, oligomers or polymers, for example, there can be listed polyols and organic diamines.
[0136] The molecular weight of the perfluorocarbon polymer in the present embodiment is not particularly limited, and the melt flow index (MFI) value measured according to ASTM:D1238 (measurement conditions: temperature is 270°C, load is 2160g) is preferably 0.05g / 10min or more and 50g / 10min or less, more preferably 0.1g / 10min or more and 30g / 10min or less, and further preferably 0.5g / 10min or more and 20g / 10min or less.
[0137] (Method for producing perfluorocarbon polymer)
[0138] The perfluorocarbon polymer in the present embodiment is not particularly limited, and can be obtained by, for example, producing a precursor of a perfluorocarbon polymer having an ion exchange group (hereinafter also referred to as a "resin precursor") and then subjecting the precursor to a hydrolysis treatment.
[0139] In the case of a PFSA resin, for example, it can be obtained by hydrolyzing a PFSA resin precursor composed of a copolymer of a fluorovinyl ether compound represented by the following formula (6) or (7) and a fluorinated olefin monomer represented by the following formula (8).
[0140] CF2=CF-O-(CF2CFXO) n -A (6)
[0141] (In formula (6), X is F or a perfluoroalkyl group having 1 to 3 carbon atoms, n is an integer of 0 to 5, and A is (CF2) m -W, where m is an integer of 0 to 6, n and m are not 0 at the same time, and W is a functional group that can be converted into a -SO3H group by hydrolysis. )
[0142] CF2=CF-O-(CF2) P -CFX(-O-(CF2) K -W) or CF2=CF-O-(CF2)P-CFX(-(CF2) L -O-(CF2) m -W) (7)
[0143] (In formula (7), X is a perfluoroalkyl group having 1 to 3 carbon atoms, P is an integer of 0 to 12, K is an integer of 1 to 5, and L is an integer of 1 to 5, wherein L, K, and m are not simultaneously 0. m is an integer of 0 to 6, and W is a functional group that can be converted into a -SO3H group by hydrolysis.)
[0144] CF2=CFZ (8)
[0145] (In formula (8), Z is H, Cl, F, a perfluoroalkyl group having 1 to 3 carbon atoms, or a cyclic perfluoroalkyl group which may contain oxygen as a ring atom.)
[0146] W in formula (6) and formula (7) is not particularly limited, and examples thereof include -SO2F group, -SO2Cl group, and -SO2Br group. In the above formula (6) and formula (7), X is CF3, W is -SO2F group, and in the above formula (8), Z is preferably F. Among them, when n=0, m=an integer of 1 to 6, X is CF3, W is -SO2F group, and Z is F, there is a tendency to obtain a solution with high hydrophilicity and high resin concentration, so it is more preferred.
[0147] The resin precursor in this embodiment can be synthesized by known means. For example, in the presence of a free radical generator such as a peroxide, a 4) group (ion exchange group precursor group) and tetrafluoroethylene (hereinafter also referred to as "TFE") and other fluorinated olefins to polymerize. The above-mentioned polymerization method is not particularly limited, and the following methods can be used, for example: a method of polymerizing by filling and dissolving the above-mentioned fluorinated vinyl compound and fluorinated olefin gas in a polymerization solvent such as fluorinated hydrocarbon and reacting them (solution polymerization); a method of polymerizing by using the fluorinated vinyl compound itself as a polymerization solvent without using a solvent such as fluorinated hydrocarbon (bulk polymerization); a method of polymerizing by filling an aqueous solution of a surfactant as a medium with the gas of the fluorinated vinyl compound and the fluorinated olefin and reacting them (emulsion polymerization); a method of polymerizing by filling an aqueous solution of a surfactant and an emulsifier such as an alcohol with the gas of the fluorinated vinyl compound and the fluorinated olefin, emulsifying and reacting them (emulsion polymerization); and a method of polymerizing by filling an aqueous solution of a suspension stabilizer with the gas of the fluorinated vinyl compound and the fluorinated olefin and reacting them (suspension polymerization), etc.
[0148] The resin precursor in this embodiment may be one prepared by any of the above-mentioned polymerization methods. Alternatively, a bulk or cone-shaped polymer obtained by adjusting polymerization conditions such as the supply amount of TFE gas may be used as the resin precursor.
[0149] The resin precursor can be fluorinated by treating the impurity terminals and structurally easily oxidized portions (CO groups, H bond portions, etc.) generated in the resin molecular structure during the polymerization reaction under fluorine gas by a known method.
[0150] Regarding the resin precursor, a part of the ion exchange group precursor group (eg, -SO2F group) may be partially (including between molecules) imidized (alkyl imidized or the like).
[0151] The molecular weight of the resin precursor is not particularly limited. The melt flow index (MFI) value measured for the precursor according to ASTM: D1238 (measurement conditions: temperature: 270°C, load: 2160 g) is preferably 0.05 g / 10 min or more and 50 g / 10 min or less, more preferably 0.1 g / 10 min or more and 30 g / 10 min or less, and further preferably 0.5 g / 10 min or more and 20 g / 10 min or less.
[0152] The shape of the resin precursor is not particularly limited, but is preferably 0.5 cm 3 The following granular form, or dispersion liquid form, powder granular form. Among them, the powder form after polymerization is more preferably used. From the perspective of cost, a film-shaped resin precursor formed by extrusion can be used.
[0153] The method for manufacturing the perfluorocarbon polymer in this embodiment from a resin precursor is not particularly limited, and there are methods such as the following: using an extruder and using a nozzle or a mold to extrude the resin precursor, and then hydrolyzing it; or in the state of the output during polymerization, that is, in the form of a dispersion, or by precipitating and filtering it to make it into a powder, and then hydrolyzing it.
[0154] Specifically, the resin precursor formed as required by the above operation can then be immersed in an alkaline reaction liquid for hydrolysis treatment. As the alkaline reaction liquid used in the hydrolysis treatment, there is no particular limitation, and examples thereof include aqueous solutions of amine compounds such as dimethylamine, diethylamine, monomethylamine and monoethylamine; aqueous solutions of hydroxides of alkali metals or alkaline earth metals. Among these, aqueous solutions of sodium hydroxide or potassium hydroxide are preferred. When an alkali metal or alkaline earth metal hydroxide is used, its content is not particularly limited, and is preferably 10% by mass or more and 30% by mass or less relative to the entire reaction solution. The above-mentioned reaction solution more preferably also contains swelling organic compounds such as methanol, ethanol, acetone and dimethyl sulfoxide (DMSO). The content of the swelling organic compound is preferably 1% by mass or more and 30% by mass or less relative to the entire reaction solution.
[0155] After the resin precursor is subjected to hydrolysis treatment in an alkaline reaction liquid, it is fully washed with warm water or the like, and then subjected to an acid treatment. The acid used in the acid treatment is not particularly limited, and examples thereof include inorganic acids such as hydrochloric acid, sulfuric acid, and nitric acid; and organic acids such as oxalic acid, acetic acid, formic acid, and trifluoroacetic acid. A mixture of these acids and water is preferred. In addition, the above acids may be used alone or in combination of two or more. In addition, the alkaline reaction liquid used in the hydrolysis treatment may be removed in advance before the acid treatment by treating it with a cation exchange resin or the like.
[0156] By acid treatment, the ion exchange group precursor group of the resin precursor is protonated to generate an ion exchange group. For example, in the case of a resin precursor manufactured using the aforementioned formula (6), W of formula (6) is protonated by acid treatment to form a -SO3H group. The perfluorocarbon polymer obtained by hydrolysis and acid treatment can be dispersed or dissolved in a protic organic solvent, water or a mixed solvent of the two, and can be made into a suspension or solution.
[0157] In the perfluorocarbon polymer, alkali metals, alkaline earth metals and free radical decomposable transition metals (Ce compounds, Mn compounds, etc.) can be contained in the form of partial salts (about 0.01 to 5 equivalent % of the total ion exchange group equivalents) formed therewith, or can be contained alone or in the form of combination with the basic polymer described later.
[0158] From the viewpoint of achieving better resistance and mechanical strength, the electrolyte membrane of the present embodiment preferably contains a mixture of two or more perfluorocarbon polymers having ion exchange groups and having different monomer structures.
[0159] By mixing two or more perfluorocarbon polymers, excellent properties can be exhibited by combining the functions of each other.
[0160] In addition, from the viewpoint of making the mechanical strength better, when two or more perfluorocarbon polymers are mixed, the ratio of the polymer with a higher equivalent mass EW is preferably greater than 50% by mass, more preferably greater than 55% by mass, and further preferably greater than 60% by mass. The polymer with a high equivalent mass EW tends to have higher crystallinity, and therefore, when the above ratio is used, there is a tendency to show higher mechanical strength.
[0161] (Method for producing raw material film of perfluorocarbon polymer)
[0162] The raw material film used in the manufacture of the electrolyte membrane of the present embodiment can be obtained by processing the precursor resin or perfluorocarbon polymer into a film using a known method. For example, the following method can be used: after the precursor of the above-mentioned perfluorocarbon polymer is melt-kneaded, a film is formed using an extruder, and then hydrolyzed to form an ion exchange group. In addition, the perfluorocarbon polymer can be temporarily dispersed in a solvent and then formed into a film by casting on a substrate.
[0163] (Method for stretching raw material film of perfluorocarbon polymer)
[0164] The method for producing an electrolyte membrane according to the present embodiment includes the step of stretching a raw material film under heating.
[0165] The manufacturing method of this embodiment further includes a step of performing a relaxation treatment during cooling after the aforementioned stretching step.
[0166] In other words, the electrolyte membrane of the present embodiment is stretched under heating and then cooled at a relaxation rate of preferably 0.1% to 5.0%, thereby having no cracks and suppressing self-discharge.
[0167] The stretching treatment in the present embodiment can be performed by, for example, uniaxial stretching, simultaneous biaxial stretching, or sequential biaxial stretching.
[0168] In the present embodiment, the X-axis direction refers to the winding direction (MD direction) when a long film is produced by extrusion film production, cast film production, etc., and the Y-axis direction refers to the direction orthogonal to the MD direction (TD direction).
[0169] From the viewpoint of suppressing the deflection of the membrane when assembled into the unit, the stretching ratio is preferably 1.5 times, more preferably 1.8 times, further preferably 2.1 times, and further preferably 2.5 times in at least a uniaxial direction. In addition, from the viewpoint of suppressing the generation of cracks and improving the selectivity of permeable ions, the stretching ratio is preferably 8 times or less, more preferably 6 times or less, further preferably 5 times or less, and further preferably 4 times or less. The stretching ratio in the present embodiment can set the stretching ratio independently in the X-axis direction and the Y-axis direction. From the viewpoint of improving the selectivity of permeable ions, the area stretching ratio obtained by multiplying the stretching ratio in the X-axis direction by the stretching ratio in the Y-axis direction is preferably 2.2 times or more, more preferably 3.2 times or more, and further preferably 4.0 times or more. From the viewpoint of suppressing the generation of cracks, the area stretching ratio is preferably 50 times or less, more preferably 40 times or less, and further preferably 30 times or less.
[0170] From the viewpoint of controlling the cluster diameter in the electrolyte membrane and further improving the ion selective permeability, biaxial stretching is preferably performed. In other words, the electrolyte membrane of the present embodiment is preferably a biaxially stretched electrolyte membrane. In the present embodiment, first, a membrane of a perfluorocarbon polymer having an ion exchange group is simultaneously biaxially stretched in a temperature range of 20°C lower than the α dispersion temperature of the polymer to 40°C higher.
[0171] The α dispersion temperature of the perfluorocarbon polymer film having an ion exchange group refers to the temperature at which the main chain of the polymer begins to thermally move, as measured by a dynamic viscoelasticity measuring device. For example, the α dispersion temperature of polymers such as nylon is usually significantly higher than room temperature. Therefore, by cooling to below the α dispersion temperature after stretching, the thermal movement of the main chain can be greatly reduced, thereby effectively stabilizing the stretching orientation.
[0172] For example, when the ion exchange groups are sulfonic acid groups, the α dispersion temperature of the perfluorocarbon polymer is around 110 to 140° C. Therefore, assuming that the α dispersion temperature is 140° C., the stretching temperature in the stretching step is set in the temperature range of 120° C. to 180° C.
[0173] Furthermore, the present embodiment is characterized in that the film stretched in the stretching step is subsequently heat-treated at a temperature higher than the stretching temperature while the film is fixed.
[0174] Fixing the membrane means fixing the periphery of the membrane so that the orientation of the stretched membrane does not loosen. Specifically, the ends of the membrane may be fixed, and a device such as a chuck tenter may be used to fix the ends of the electrolyte membrane.
[0175] From the viewpoint of suppressing orientation relaxation, the stretching speed during the stretching treatment is preferably 10 mm / min or more, more preferably 50 mm / min or more, and further preferably 90 mm / min or more. On the other hand, from the viewpoint of suppressing breakage, the stretching speed is preferably 500 mm / min or less, more preferably 300 m / min or less, and further preferably 200 m / min or less.
[0176] The method for producing an electrolyte membrane according to the present embodiment preferably further includes a step of performing a relaxation treatment during cooling after the stretching treatment.
[0177] The relaxation treatment after the stretching treatment in this embodiment is performed by narrowing the chuck interval by a predetermined distance. From the viewpoint of suppressing fracture, the ratio of the narrowed distance to the chuck interval (relaxation rate) is preferably 0.1% or more, more preferably 0.2% or more, and further preferably 0.4% or more. On the other hand, from the viewpoint of suppressing orientation relaxation, it is preferably 3% or less, more preferably 2% or less, and further preferably 1.5% or less. Thereby, the stress caused by shrinkage during cooling can be relaxed, and a stretched film can be obtained without generating micro defects in the film. When a redox flow battery is formed, even if the electrolyte membrane swells in the electrolyte, an electrolyte membrane with excellent permeable ion selectivity can be obtained.
[0178] The method for manufacturing the electrolyte membrane of the present embodiment preferably further includes: after the above-mentioned relaxation treatment step, a step of heat treating the obtained membrane in a constrained state for 1 minute to 30 minutes at a temperature above the glass transition temperature and below a temperature 100°C higher than the glass transition temperature.
[0179] The temperature of the heat treatment step is preferably 80° C. to 200° C., more preferably 90° C. to 180° C., and further preferably 90° C. to 160° C. The heat treatment time is preferably 1 minute to 20 minutes, and more preferably 1 minute to 15 minutes.
[0180] (Flatness)
[0181] From the perspective of good operability when assembling a redox flow battery, the flatness index of the electrolyte membrane of the present embodiment is preferably less than 1.2, more preferably less than 1.1, and further preferably less than 1.05. The flatness index of the electrolyte membrane is the ratio of the length along the membrane surface to the projected size of the membrane. The specific measurement method is as described in the examples. The flatness index of the electrolyte membrane can satisfy the above values on any surface, preferably on any surface cut into 140 mm square.
[0182] (Crack area ratio)
[0183] From the viewpoint of suppressing self-discharge, the crack area ratio in the electrolyte membrane of the present embodiment is 1.5% or less.
[0184] From the viewpoint of suppressing self-discharge, the crack area ratio is preferably 1.3% or less, more preferably 1.0% or less, and further preferably 0.8% or less. For example, the crack area ratio is preferably 0.0% or more, and from the viewpoint of improving puncture strength, it is more preferably 0.1% or more, and further preferably 0.2% or more.
[0185] The crack area refers to the ratio of the area of the region with a transmittance of 10% or less to the total area of the electrolyte membrane. The crack area can be determined by measuring the visible light transmittance distribution in the electrolyte membrane surface, and more specifically, can be measured by the method described in the Examples.
[0186] (Orientation parameter)
[0187] From the viewpoint of permeation ion selectivity, the orientation parameter of the present embodiment is preferably 0.05 or more, more preferably 0.15 or more, and further preferably 0.20 or more in either the membrane surface or the surface perpendicular to the membrane surface (outside the membrane surface). The upper limit of the orientation parameter is not particularly limited, but from the viewpoint of suppressing the reduction in membrane strength caused by the generation of cracks, it is preferably 0.70 or less, more preferably 0.60 or less, and further preferably 0.50 or less.
[0188] From the viewpoint of suppressing self-discharge, the orientation parameter of the plane perpendicular to the film surface (hereinafter also referred to as "film out-of-plane orientation parameter") is preferably 0.15 or more, more preferably 0.20 or more, and further preferably 0.25 or more. The upper limit of the orientation parameter of the plane perpendicular to the film surface is not particularly limited, but is preferably 0.70 or less, more preferably 0.60 or less, and further preferably 0.50 or less.
[0189] By orienting the electrolyte membrane under specific conditions in a manner that achieves the above-mentioned range of orientation parameters, the cluster shape in the membrane thickness direction can be controlled to form a membrane in which fine defects, i.e., cracks, within the membrane are suppressed. As a result, the permeation of vanadium ions and other plasma and electrolyte can be effectively suppressed without suppressing the movement of protons.
[0190] The orientation parameters q in and out of the film plane can be obtained by approximating the azimuthal intensity distribution I(φ) of the peak derived from the ion cluster in the small-angle X-ray scattering described below using the orientation function shown in the following formula.
[0191] [Mathematical formula 1]
[0192]
[0193] Here, Q is a constant, φ is the azimuth angle, and q is the orientation parameter.
[0194] (Ion cluster diameter)
[0195] The ion cluster diameter of the present embodiment can be measured in the film surface direction and in the direction perpendicular to the film surface by small angle X-ray scattering (SAXS).
[0196] From the viewpoint of reducing the resistance component when forming a redox flow battery, the ion cluster diameter in the membrane surface direction is preferably 2.5 nm or more, more preferably 2.7 nm or more, and further preferably 2.8 nm or more. In addition, from the viewpoint of suppressing the penetration of active materials in the electrolyte and improving the current efficiency, the ion cluster diameter in the membrane surface direction is preferably 3.9 nm or less, more preferably 3.5 nm or less, and further preferably 3.2 nm or less.
[0197] From the viewpoint of improving the permeation ion selectivity, the ion cluster diameter in the direction perpendicular to the membrane surface (hereinafter referred to as "the ion cluster diameter in the membrane surface outer direction") is preferably 3.0 nm or more, more preferably 3.3 nm or more, and further preferably 3.4 nm or more. The ion cluster diameter in the membrane surface outer direction is not particularly limited, but is preferably 3.9 nm or less, more preferably 3.7 nm or less, and further preferably 3.6 nm or less.
[0198] (Long crystallization period)
[0199] The crystal long period of the electrolyte membrane of the present embodiment measured by small angle X-ray scattering is obtained as follows: -1 The position of the periodic peak originating from the electron density difference between the crystal and the amorphous phase generated within the range of is determined using the Bragg equation.
[0200] The crystal long period measured by small-angle X-ray scattering is preferably 5 nm to 60 nm, more preferably 10 nm to 55 nm, further preferably 20 nm to 50 nm, and still further preferably 30 nm to 50 nm.
[0201] The peak intensity of the long-period crystal measured by small-angle X-ray scattering is 0.1 to 1.0 nm when the scattering vector of the small-angle X-ray scattering is 0.1 to 1.0 nm. -1 The peak intensity is defined as the ratio of the difference between the peak intensity of the crystalline long period peak generated within the range of 0.5 and the baseline intensity to the baseline intensity. From the viewpoint of improving current efficiency, the peak intensity is preferably 0.5 or less, more preferably 0.3 or less, further preferably 0.2 or less, and further preferably 0.1 or less.
[0202] Regarding the film thickness of the raw material film to be stretched in the present embodiment, a film having a thickness calculated based on a target stretching ratio can be used.
[0203] From the viewpoint of operability of the membrane, the thickness of the electrolyte membrane of the present embodiment is preferably 1 μm or more, more preferably 3 μm or more, and further preferably 5 μm or more. In addition, from the viewpoint of cell resistance when used as a redox flow battery, the thickness of the electrolyte membrane is preferably 500 μm or less, more preferably 300 μm or less, further preferably 100 μm or less, further preferably 70 μm or less, and further preferably 40 μm or less.
[0204] The electrolyte membrane of this embodiment can be suitably used as a diaphragm of a redox flow battery. Generally speaking, an electrolyte membrane composed of a perfluorocarbon polymer having an ion exchange group swells and changes in size when it contacts an aqueous solution such as an electrolyte, an aqueous sulfuric acid solution, or distilled water. The electrolyte membrane of this embodiment can suppress swelling even when it contacts these aqueous solutions, and the dimensional change in the membrane surface direction is suppressed. Therefore, when assembling a unit of a redox flow battery, even if the electrolyte membrane is used without swelling it in advance and filled with an electrolyte, it can be used without causing the membrane to bend or reducing the battery performance.
[0205] (Dimensional change rate caused by immersion in 2M sulfuric acid aqueous solution)
[0206] From the perspective of preventing deflection in the redox flow battery unit and reducing battery performance, the dimensional change rate of the electrolyte membrane of this embodiment caused by immersion in a 2M sulfuric acid aqueous solution is 80% or more and less than 100% in at least one of the X direction and the Y direction.
[0207] <Dimensional change rate caused by immersion in 2M sulfuric acid aqueous solution>
[0208] The test electrolyte membrane was adjusted to have a water content of 1% or less, and immersed in a 2M sulfuric acid aqueous solution at 25°C for 30 minutes. The dimensional change rate in the X direction on the surface of the test electrolyte membrane and in the Y direction orthogonal to the X direction was calculated by the following formula.
[0209] Dimension change rate (%) = {(dimension in a specific direction after immersion) / (dimension in a specific direction before immersion)}×100
[0210] From the viewpoint of preventing deflection in the cell of the redox flow battery and reducing battery performance, the dimensional change rate of the electrolyte membrane of the present embodiment in a 2M sulfuric acid aqueous solution is preferably 99.8% or less, more preferably 99.5% or less, further preferably 99.2% or less, and further preferably 99.0% or less. From the viewpoint of reducing stress and achieving good long-term durability, the dimensional change rate of at least one of the X direction and the Y direction is preferably 85% or more, more preferably 90% or more, further preferably 95.0% or more, and further preferably 97.0% or more.
[0211] More specifically, the dimensional change rate caused by immersion in a 2M sulfuric acid aqueous solution can be evaluated by, for example, adjusting the water content of the electrolyte membrane to less than 1%, cutting it into a square with a single side of 7 cm, and measuring the size after immersing it in a 2M sulfuric acid aqueous solution at 25°C for 30 minutes. The water content can be measured using the method described in the Examples. When the water content exceeds 1%, it can be adjusted by drying it in an oven heated to 50°C under reduced pressure for 2 hours and measuring the water content again.
[0212] It should be noted that the X direction is an arbitrary direction on the film surface, and the Y direction refers to a direction perpendicular to the X direction on the film surface.
[0213] The dimensional change rate due to immersion in a 2M sulfuric acid aqueous solution can be adjusted to the above range by, for example, adjusting the type of perfluorocarbon polymer used in the electrolyte membrane, the stretching ratio during the production of the electrolyte membrane, the relaxation ratio, and the like.
[0214] (Dimensional change rate caused by distilled water immersion)
[0215] From the viewpoint of preventing deflection in the unit of the redox flow battery and reducing battery performance, the dimensional change rate of the electrolyte membrane of this embodiment caused by immersion in distilled water is greater than 80% and less than 100% in at least one of the X and Y directions, and greater than 115% in the Z direction.
[0216] From the viewpoint of preventing deflection in the cell of the redox flow battery and reducing battery performance, the dimensional change rate in at least one of the X direction and the Y direction due to immersion in distilled water is preferably 99.8% or less, more preferably 99.5% or less, further preferably 99.2% or less, and further preferably 99.0% or less. From the viewpoint of reducing stress and achieving good long-term durability, the dimensional change rate in at least one of the X direction and the Y direction is preferably 85% or more, more preferably 90% or more, further preferably 93.0% or more, and further preferably 94.0% or more.
[0217] From the viewpoint of water retention and improvement of proton conductivity, the dimensional change rate in the Z direction of the dimensional change rate caused by distilled water immersion is preferably 115% or more, more preferably 120% or more, and further preferably 125% or more. From the viewpoint of permeation ion selectivity, the dimensional change rate in the Z direction is preferably 160% or less, more preferably 150% or less, further preferably 140% or less, and further preferably 130% or less.
[0218] More specifically, the dimensional change rate caused by distilled water immersion can be evaluated by adjusting the water content of the electrolyte membrane to less than 1%, cutting it into a square with a single side of 7 cm, and measuring the size after immersing it in distilled water at 25°C for 30 minutes. The water content can be measured by the method described in the examples. When the water content exceeds 1%, it can be adjusted by drying it in an oven heated to 50°C for 2 hours under reduced pressure and measuring the water content again.
[0219] It should be noted that the X direction is an arbitrary direction on the film surface, the Y direction refers to a direction on the film surface perpendicular to the X direction, and the Z direction refers to a direction orthogonal to the X direction and the Y direction.
[0220] The dimensional change rate in the dimensional change rate due to immersion in distilled water can be set to the above range by adjusting, for example, the type of perfluorocarbon polymer used in the electrolyte membrane, the stretching ratio and the relaxation ratio when producing the electrolyte membrane.
[0221] (Puncture Strength)
[0222] The puncture strength of the electrolyte membrane of this embodiment based on the following puncture strength test is preferably 0.01kgf / μm or more, more preferably 0.02kgf / μm or more, further preferably 0.03kgf / μm or more, further preferably 0.04kgf / μm or more, and further preferably 0.05kgf / μm or more. The upper limit of the puncture strength is not particularly limited, for example, 0.10kgf / μm or less.
[0223] <Puncture Strength Test>
[0224] For an electrolyte membrane that has been left at room temperature for more than 12 hours, a needle with a curvature radius of 0.5 mm was used to pierce the electrolyte membrane sandwiched between two metal plates with a circular hole of 10 mm in diameter at a speed of 2 mm / sec. The value obtained by dividing the maximum load (kgf) of the load-displacement curve by the thickness (μm) of the electrolyte membrane was recorded as the puncture strength (kgf / μm).
[0225] (Anion exchange compound)
[0226] The electrolyte membrane of this embodiment is preferably covered with an anion exchange compound on at least one side. By covering the surface with an anion exchange compound, the current efficiency can be improved, and the performance of the battery can be improved. The anion exchange compound mentioned here refers to a compound having a basic functional group such as a primary to tertiary amino group, a quaternary ammonium group, etc. in the molecular structure and being positively charged under at least an acidic condition of pH = 1.
[0227] By coating the electrolyte membrane surface with an anion exchange compound, electrostatic repulsion can be applied to the electrolyte membrane surface, metal ions with high charge density are excluded from the electrolyte membrane, and protons with low charge density are selectively allowed to pass through the membrane, thereby improving current efficiency.
[0228] From the viewpoint of further improving current efficiency, the anion exchange compound preferably has a tertiary amino group or a quaternary ammonium group.
[0229] The anion exchange compound is not particularly limited, and examples thereof include cationic polymers such as polyvinylpyridine, polyethyleneimine, vinylbenzyltrimethylammonium chloride / divinylbenzene copolymer, polybenzimidazole, pyrrole, dodecyltrimethylammonium, and cetylpyridinium. Among these, polyvinylpyridine and dodecyltrimethylammonium are preferred.
[0230] (Surface covering method using anion exchange compound)
[0231] Methods for covering the electrolyte membrane with anion exchange compounds include, for example, a method of immersing the electrolyte membrane in a liquid in which the anion exchange compound is dissolved or melted; a method of applying the liquid in which the anion exchange compound is dissolved or melted to the electrolyte membrane; and a method of hot-pressing a thin film formed by the anion exchange compound to the electrolyte membrane. The method is not limited as long as the anion exchange compound can be concentrated on the surface of the electrolyte membrane.
[0232] The electrolyte membrane of the present embodiment is preferably used in a redox flow battery.
[0233] In particular, excellent battery performance is exhibited in a method of using the dried electrolyte membrane incorporating it into a cell.
[0234] [Redox flow battery]
[0235] Figure 1An example of a schematic diagram of a redox flow secondary battery obtained using the electrolyte membrane for a redox flow battery of the present embodiment is shown. The redox flow secondary battery 10 of the present embodiment has an electrolytic cell 6, wherein the electrolytic cell 6 includes: a positive electrode cell 2 including a positive electrode 1 formed by a carbon electrode, a negative electrode cell 4 including a negative electrode 3 formed by a carbon electrode, and an electrolyte membrane 5 as a diaphragm that isolates the positive electrode cell 2 from the negative electrode cell 4, wherein the positive electrode cell 2 includes: a positive electrode electrolyte containing an active material, and the negative electrode cell 4 includes: a negative electrode electrolyte containing an active material. The positive electrode electrolyte and the negative electrode electrolyte containing the active material are stored using, for example, a positive electrode electrolyte tank 7 and a negative electrode electrolyte tank 8, and are supplied to each cell using a pump or the like. In addition, the current generated by the redox flow secondary battery can be converted from direct current to alternating current with the aid of an alternating current to direct current conversion device 9.
[0236] The redox flow secondary battery obtained using the redox flow battery electrolyte membrane of this embodiment has the following structure: liquid-permeable and porous collector electrodes (for negative electrode and positive electrode) are respectively arranged on both sides of the diaphragm, and they are clamped by pressing, and the side separated by the diaphragm is used as the positive electrode unit chamber, and the other side is used as the negative electrode unit chamber, and a spacer is used to ensure the thickness of the two unit chambers.
[0237] In the case of a vanadium-based redox flow secondary battery, a substance containing tetravalent vanadium (V 4+ ) and pentavalent vanadium (V 5+ ) is used as the positive electrode electrolyte, and a sulfuric acid electrolyte containing trivalent vanadium (V 3 + ) and divalent vanadium (V 2+ ) of the negative electrode electrolyte, thereby charging and discharging the battery. Therefore, the positive electrode electrolyte and the negative electrode electrolyte in the redox flow battery of this embodiment preferably contain vanadium ions. At this time, during charging, in the positive electrode unit chamber, the vanadium ions release electrons, so V 4+ Oxidized to V 5+ , in the negative electrode cell, due to the electrons returning through the external path, V 3+ Restored to V 2+ In this redox reaction, in the positive electrode unit cell, protons (H + ) becomes excessive, while in the negative electrode unit cell, protons (H +) is insufficient. The diaphragm selectively moves excess protons in the positive electrode unit chamber to the negative electrode chamber, thereby maintaining electrical neutrality. During discharge, the reverse reaction occurs. The current efficiency (%) at this time is expressed as the ratio (%) obtained by dividing the discharge amount by the charge amount. The two amounts depend on the internal resistance of the battery cell and the ion selectivity of the diaphragm and other current losses. A reduction in internal resistance will increase voltage efficiency, and an increase in ion selectivity and a reduction in other current losses will increase current efficiency, and therefore become an important indicator for redox flow secondary batteries.
[0238] <Carbon Electrode>
[0239] The carbon electrode used in the redox flow secondary battery is not particularly limited, but preferably has continuous pores to allow the electrolyte to pass therethrough, and is more preferably a porous body having continuous pores.
[0240] In addition, the carbon electrode with continuous voids preferably contains fibrous carbon. In addition, the average fiber diameter of the fibrous carbon is preferably less than 5 μm, more preferably less than 4 μm, and further preferably less than 3 μm. Thus, the surface area can be increased while maintaining the flexibility of the electrode, and a redox flow secondary battery with high current efficiency, low resistance and good performance can be obtained. The lower limit of the average fiber diameter is not particularly limited, and may be greater than 0.1 μm, greater than 0.5 μm, or greater than 1 μm. The method for determining the average fiber diameter is based on the method described in the embodiments. In addition, the carbon electrode is preferably a three-dimensional continuous carbon structure.
[0241] The carbon electrode with continuous voids is not particularly limited, and examples thereof include carbon felt, carbon paper, and carbon foam. Among these, carbon foam is more preferred from the viewpoint of high flexibility, large surface area, and ability to reduce resistance. The carbon foam preferably has a three-dimensional continuous structure of the carbon portion. The carbon foam preferably has a linear portion and a bonding portion that bonds the aforementioned linear portion. By having this structure, an electrode with high flexibility and surface area can be made, and even if a thinner film is used for the electrolyte membrane of the redox flow secondary battery, the current efficiency will not be reduced, and a good battery can be obtained.
[0242] Carbon foam can also be compressed by a known method, especially the method described in International Publication No. 2002 / 062879, and the porosity can be adjusted before use. By compressing and adjusting the porosity, the carbon surface area per unit volume can be increased, thereby reducing the resistance of the redox flow secondary battery.
[0243] The density of the carbon foam joints is preferably 15,000 / mm 3 More preferably, 30,000 pieces / mm 3 More preferably, 50,000 pieces / mm 3More preferably, 100,000 pieces / mm 3 In addition, from the viewpoint of ensuring space for the linear portion and the connecting portion to deform during compression, the density of the connecting portion is preferably 5,000,000 pieces / mm 3 Less than, more preferably 4,000,000 pieces / mm 3 Below, more preferably 3,500,000 pieces / mm 3 the following.
[0244] It is sufficient that at least a portion of the carbon foam of this embodiment has a portion satisfying the density of the bonding portion. It is preferred if 50% by volume satisfies the above density range, and it is more preferred if 75% by volume satisfies the above density range. It is particularly preferred that any portion of the carbon foam satisfies the above density range.
[0245] (The number of linear portions N l Relative to the number of joints N n Ratio R)
[0246] In the carbon foam of the present embodiment, the number N of the linear portions is 1000 Å from the viewpoint of the firmness of the three-dimensional structure and the maintenance of the flexibility against pressure. l Relative to the number of joints N n The ratio R is preferably 1.2 or more, more preferably 1.3 or more, and further preferably 1.4 or more. In addition, the ratio R is preferably 1.7 or less, more preferably 1.6 or less, and further preferably 1.5 or less.
[0247] In other words, the ratio R is the average number of branches branching from the bonded portion. In the case of a structure in which unbonded linear portions are in contact, such as a nonwoven fabric, the ratio R is a small value. On the other hand, in the case of a porous structure in which the linear portions are band-shaped, such as a structure covered with a honeycomb-shaped wall, the ratio R is a large value.
[0248] In addition, in this specification, the number N of the above-mentioned joints is n , the number of linear parts N lThis is a value obtained by photographing carbon foam using an X-ray CT (Computerized Tomography) device, using a Median filter as pre-processing based on the obtained tomographic image data, and then using Otsu's binarization algorithm (refer to "Automatic threshold selection method based on the least squares criterion for judgment and discrimination", Proceedings of the Institute of Electronics, Information and Communications Technology D, Vol. J63-D, No. 4, pp. 346-356 (1980)) to perform structural and spatial region segmentation, and create a three-dimensional image of the structure including the inside of the carbon foam, and using structural analysis software to obtain the value from the obtained three-dimensional image.
[0249] Specifically, the number of joints N n and the number of linear portions N l The N obtained by the above operation can be obtained by detecting the joints and linear portions included in the three-dimensional image and counting their number. n and N l To find N l Relative to N n The ratio R.
[0250] (Carbon content)
[0251] The carbon content of the carbon foam can be determined by fluorescent X-ray measurement. From the viewpoint of electrical conductivity, the carbon content of the carbon foam of the present embodiment is preferably 51% by mass or more, preferably 60% by mass or more, preferably 65% by mass or more, preferably 70% by mass or more, preferably 75% by mass or more, preferably 80% by mass or more, more preferably 85% by mass or more, and further preferably 90% by mass or more. The upper limit of the carbon content is not particularly limited, and may be 100% by mass or less, or 99% by mass or less.
[0252] The carbon content of the carbon foam can be determined by fluorescent X-ray measurement.
[0253] (Porosity)
[0254] From the viewpoint of flexibility, the porosity of the carbon foam of the present embodiment is preferably 50% by volume or more, more preferably 60% by volume or more, further preferably 70% by volume or more, further preferably 80% by volume or more, and further preferably 90% by volume or more. The upper limit of the porosity is not particularly limited, and may be less than 100% by volume, may be 99% by volume or less, may be 98% by volume or less, and may be 95% by volume or less.
[0255] It should be noted that in this specification, the porosity is a value obtained from the following bulk density and the following true density. The bulk density is a density obtained based on the volume including the voids contained in the carbon foam. In contrast, the true density is a density obtained based on the volume occupied by the material of the carbon foam.
[0256] <<Determination of Bulk Density>>
[0257] First, the size of the carbon foam is measured using a vernier caliper or the like, and the bulk volume V of the carbon foam is calculated from the obtained size. bulk Next, the mass M of the carbon foam was measured using a precision balance. Based on the obtained mass M and bulk volume V bulk Using the following formula (a), the volume density of carbon foam can be calculated as bulk .
[0258] ρ bulk =M / V bulk ···(a)
[0259] <<Determination of True Density>>
[0260] True density of carbon foam ρ real A mixed solution containing n-heptane, carbon tetrachloride and ethylene dibromide can be used and obtained by the floatation and sinking method. Specifically, first, a carbon foam of appropriate size is placed in a stoppered test tube. Next, the three solvents are appropriately mixed and added to the test tube, and immersed in a constant temperature bath at 30°C. In the case where the test piece floats, add low-density n-heptane. On the other hand, in the case where the test piece sinks, add high-density ethylene dibromide. Repeat this operation to make the test piece float in the liquid. Finally, use a Gay-Lussac pycnometer to measure the liquid density.
[0261] <<Calculation of void ratio>>
[0262] According to the volume density ρ obtained above bulk and true density ρ real , the porosity V is calculated using the following formula (b): f,pore .
[0263] V f,pore ={((1 / ρ bulk )-(1 / ρ real )) / (1 / ρ bulk )}×100(%)···(b)
[0264] (Crystallite size)
[0265] The crystallite size Lc of the carbon foam of this embodiment is preferably 1.1 nm or more, and more preferably 1.5 nm or more from the viewpoint of conductivity. In addition, from the viewpoint of physical fragility, it is preferably 4.0 nm or less, and more preferably 3.0 nm or less. The crystallite size Lc is measured by the following method.
[0266] <<Evaluation of crystallite size>>
[0267] The crystallite size Lc was evaluated based on the diffraction of the (002) plane of the carbon foam. The sample was crushed in a mortar and then crushed using a desktop X-ray diffractometer D2 PHASER (manufactured by Bluker Corporation), and the obtained sample was subjected to wide-angle X-ray measurement. The specific measurement conditions are as follows.
[0268] -Measurement conditions-
[0269] Radioactive source: Cu Kα
[0270] Tube current: 30mA
[0271] Tube voltage: 40kV
[0272] Slit: 1mm
[0273] Sample rotation speed: 10 rpm
[0274] Measurement time for 1 step: 0.3 sec
[0275] Start angle (2θ): 5.00°
[0276] Measurement step (2θ): 0.01°
[0277] End angle (2θ): 90.00°
[0278] After the above measurement, the obtained data is analyzed to calculate the crystallite size Lc. In the calculation of the crystallite size Lc, the half-value width β of the diffraction peak of the (002) plane appearing near 2θ=25 degrees and the angle θ of the peak maximum can be substituted into the following formula (c) (Scherrer formula) to obtain it. Generally speaking, the higher the carbonization temperature, the higher the crystallinity and the larger the Lc value.
[0279] Lc=(Kλ) / βcosθ···(c)
[0280] Here, K is the shape factor and λ is the wavelength of the radiation source. The shape factor is (002) plane diffraction, so 0.90 is substituted. Since CuKα is used this time, 1.541 is substituted for the radiation source for calculation.
[0281] (Average fiber diameter)
[0282] The carbon foam of the present embodiment preferably contains fibrous carbon. The average fiber diameter of the fibrous carbon is preferably 5 μm or less, more preferably 4 μm or less, and further preferably 3 μm or less. Thus, the surface area can be increased while maintaining the flexibility of the electrode, and a redox flow secondary battery with high current efficiency, low resistance and good performance can be obtained. The lower limit of the average fiber diameter is not particularly limited, and can be 0.1 μm or more, 0.5 μm or more, or 1 μm or more. The method for determining the average fiber diameter is based on the method described in the examples.
[0283] (Specific surface area)
[0284] The specific surface area S is preferably 0.5 m 2 / g or more, more preferably 1m 2 / g or more. This can increase the reaction site of the redox flow battery and form a good battery with low resistance. The upper limit of the specific surface area S is not particularly limited and can be 100m 2 / g or less, can be 50m 2 / g or less, can be 30m 2 / g or less, can be 15m 2 / g or less, and can also be 10m 2 / g or less. The specific surface area S is obtained from the true density of the carbon electrode and the average fiber diameter of the fibrous carbon constituting the carbon electrode. More specifically, the specific surface area S is obtained by the following method.
[0285] <<Calculation of specific surface area S>>
[0286] The specific surface area S of the carbon electrode is calculated as follows: Assuming that the shape of the fibrous carbon is cylindrical, the true density ρ calculated as above is real The average fiber diameter was determined using the following formula (d).
[0287] S = 4 / (ρ real × average fiber diameter)···(d)
[0288] (Proportion of graphite and surface functional group concentration)
[0289] In the carbon foam of the present embodiment, the ratio of graphite in the carbon atoms measured by X-ray photoelectron spectroscopy can be 70 at% or more and 80 at% or less. By making the ratio of graphite 70 at% or more, when the carbon foam is used in the structure of the secondary battery electrode, low resistance can be stably maintained for long-term charge and discharge. In addition, by making the ratio of graphite 80 at% or less, wettability in the electrolyte can be improved.
[0290] Furthermore, alternatively or additionally, in the carbon foam of the present embodiment, the ratio of carbon atoms having hydroxyl groups among carbon atoms measured by X-ray photoelectron spectroscopy can be 5 at% or more and 15 at% or less. By making this ratio 5 at% or more, wettability in an electrolyte can be improved. In addition, by making this ratio 15 at% or less, in the configuration of using the carbon foam for a secondary battery electrode, low resistance can be stably maintained for long-term charge and discharge.
[0291] Furthermore, alternatively or additionally, in the carbon foam of the present embodiment, the ratio of carbon atoms constituting carbonyl groups among carbon atoms measured by X-ray photoelectron spectroscopy can be 10 at% or more and 15 at% or less. By making this ratio 10 at% or more, wettability in an electrolyte can be improved. In addition, by making this ratio 15 at% or less, in the configuration of using the carbon foam for a secondary battery electrode, low resistance can be stably maintained for long-term charge and discharge.
[0292] Furthermore, alternatively or additionally, in the carbon foam of the present embodiment, the ratio of carbon atoms constituting carboxyl groups among carbon atoms measured by X-ray photoelectron spectroscopy can be 0.1 at% or more and 5 at% or less. By making this ratio 0.1 at% or more, wettability in an electrolyte can be improved. In addition, by making this ratio 5 at% or less, in the configuration of using the carbon foam for a secondary battery electrode, low resistance can be stably maintained for long-term charge and discharge.
[0293] <<Measurement Method of Graphite Ratio and Functional Group Concentration>>
[0294] In this specification, the surface analysis of carbon foam based on X-ray photoelectron spectroscopy is performed as follows. The concentration of oxygen-containing functional groups on the surface of carbon foam can be measured using an X-ray photoelectron spectrometer (PerkinElmer, ESCA-5500MT). The obtained C1s peak is fitted using four Gaussian distributions with bond energies of 284.4 eV (graphite), 285.6 eV (C-OH), 287.0 eV (C=O) and 288.6 eV (COOH) as peaks, and the ratio of the area of each peak to the total area of the four peaks is calculated, thereby being able to measure the surface functional group concentration.
[0295] (Method for producing carbon foam)
[0296] Carbon foam can be produced by, for example, carbonizing a foamed resin. During carbonization, the skeleton structure of the foamed resin used as a raw material is maintained and carbonization is performed. From the viewpoint of the permeability of the electrolyte after carbonization, the foamed resin used as a raw material preferably has continuous voids. The foamed resin used as a raw material preferably has a linear portion and a bonding portion for bonding the linear portions, and the resin portion has a three-dimensional continuous structure, and melamine foam can be cited as an example.
[0297] The carbon foam of the present embodiment can be obtained by applying a compressive load to a foaming resin as a material, and performing a heat treatment in an inert gas flow such as nitrogen or an inert atmosphere such as a vacuum to carbonize it. At this time, it is important to set the heat treatment temperature to a temperature above the softening point of the foaming resin. In this way, the density of the bonding part in the carbon foam can be increased, and the fibrous carbon constituting the carbon foam can be oriented in a direction perpendicular to the direction of application of the compressive load, so that the orientation of the fibrous carbon has anisotropy.
[0298] For example, when melamine resin foam is used as the foaming resin, as the melamine resin foam, for example, a melamine / formaldehyde condensation foam produced by the method disclosed in Japanese Patent Application Laid-Open No. 4-349178 can be used.
[0299] According to the above method, first, an aqueous solution or dispersion containing a melamine / formaldehyde pre-condensate, an emulsifier, a gasifiable foaming agent, a curing agent and, if necessary, a known filler is foamed and then cured to obtain a melamine / formaldehyde condensation foam.
[0300] In the above method, as the melamine / formaldehyde pre-condensate, for example, a substance with a melamine:formaldehyde ratio of 1:1.5 to 1:4 and an average molecular weight of 200 to 1000 can be used. In addition, as an emulsifier, for example, sodium salts of alkylsulfonic acids and arylsulfonic acids can be listed in an amount of 0.5 to 5% by mass (based on the melamine / formaldehyde pre-condensate, the same below), as a gasifying foaming agent, for example, pentane and hexane can be listed in an amount of 1 to 50% by mass, and as a curing agent, for example, hydrochloric acid and sulfuric acid can be listed in an amount of 0.01 to 20% by mass. For the foaming treatment and the curing treatment, it is sufficient to heat the solution containing the above components to a temperature set according to the type of the gasifying foaming agent used.
[0301] The heat treatment temperature of the melamine resin foam during carbonization is set to be above the softening point (300 to 400° C.) of the melamine resin foam. The heat treatment temperature is preferably 800° C. or above, and more preferably 1000° C. or above. In addition, from the viewpoint of physical fragility caused by high crystallinity, the heat treatment temperature is preferably 3000° C. or below, and more preferably 2500° C. or below.
[0302] From the viewpoint of imparting anisotropy, the compressive load applied to the carbon foam is preferably 50 Pa or more, more preferably 200 Pa or more. From the viewpoint of maintaining a three-dimensional structure, the compressive load is preferably 2000 Pa or less, more preferably 1500 Pa or less.
[0303] In addition, when a vacuum pressurizing device is used for compression, it is necessary to use a spacer to determine the film thickness after compression, and control the compression ratio obtained by dividing the original thickness by the thickness of the spacer. At this time, from the viewpoint of making it anisotropic, the compression ratio is preferably 4 times or more, and more preferably 10 times or more. In addition, from the viewpoint of maintaining a three-dimensional structure, the compression ratio is preferably 100 times or less, and more preferably 50 times or less.
[0304] It should be noted that the compressive stress applied to the resin foam may be applied not only in one direction but also in two directions.
[0305] In the redox flow secondary battery 10 of the present embodiment, by using the above-described carbon foam as the positive electrode 1 formed of a carbon electrode, the cell resistance can be suppressed to a low level, and the current efficiency can be further improved.
[0306] As mentioned above, this specification discloses the following embodiments.
[0307] [A] An electrolyte membrane for a redox flow battery, comprising a perfluorocarbon polymer having ion exchange groups,
[0308] The perfluorocarbon polymer has an equivalent mass EW of ion exchange groups of 600 g / eq or more and 2000 g / eq or less,
[0309] Among the dimensional changes of the electrolyte membrane caused by immersion in a 2M sulfuric acid aqueous solution, the dimensional change in at least one of the X direction and the Y direction is 80% or more and less than 100%.
[0310] <Dimensional change rate caused by immersion in 2M sulfuric acid aqueous solution>
[0311] A test electrolyte membrane having a moisture content of 1% or less was prepared, and the test electrolyte membrane was immersed in a 2M sulfuric acid aqueous solution at 25°C for 30 minutes. The dimensional change rate in the X direction on the surface of the test electrolyte membrane and in the Y direction orthogonal to the X direction was calculated by the following formula.
[0312] Dimension change rate (%) = {(dimension in a specific direction after immersion) / (dimension in a specific direction before immersion)}×100
[0313] [B] An electrolyte membrane for a redox flow battery, comprising a perfluorocarbon polymer having ion exchange groups,
[0314] The perfluorocarbon polymer has an equivalent mass EW of ion exchange groups of 600 g / eq or more and 2000 g / eq or less,
[0315] Among the dimensional changes of the electrolyte membrane caused by immersion in distilled water, the dimensional change in at least one of the X direction and the Y direction is 80% or more and less than 100%, and the dimensional change in the Z direction is 115% or more.
[0316] <Dimensional change rate caused by distilled water immersion>
[0317] A test electrolyte membrane having a moisture content of less than 1% was prepared, and the test electrolyte membrane was immersed in distilled water at 25° C. for 30 minutes. The dimensional change rates in the X direction, the Y direction orthogonal to the X direction, and the Z direction orthogonal to the X and Y directions on the surface of the test electrolyte membrane were calculated.
[0318] Dimension change rate (%) = {(dimension in a specific direction after immersion) / (dimension in a specific direction before immersion)}×100
[0319] [C] A method for producing an electrolyte membrane for a redox flow battery, comprising:
[0320] a step of stretching a raw material film containing a perfluorocarbon polymer having an ion exchange group,
[0321] The perfluorocarbon polymer has an equivalent mass EW of ion exchange groups of 600 g / eq or more and 2000 g / eq or less,
[0322] The crack area ratio in the electrolyte membrane is 1.5% or less,
[0323] Among the dimensional changes of the electrolyte membrane caused by immersion in a 2M sulfuric acid aqueous solution, the dimensional change in at least one of the X direction and the Y direction is 80% or more and less than 100%.
[0324] <Dimensional change rate caused by immersion in 2M sulfuric acid aqueous solution>
[0325] A test electrolyte membrane having a moisture content of 1% or less was prepared, and the test electrolyte membrane was immersed in a 2M sulfuric acid aqueous solution at 25°C for 30 minutes. The dimensional change rate in the X direction on the surface of the test electrolyte membrane and in the Y direction orthogonal to the X direction was calculated by the following formula.
[0326] Dimension change rate (%) = {(dimension in a specific direction after immersion) / (dimension in a specific direction before immersion)}×100
[0327] [D] A method for producing an electrolyte membrane for a redox flow battery, comprising:
[0328] A step of stretching a raw material film containing a perfluorocarbon polymer having an ion exchange group under heating,
[0329] The perfluorocarbon polymer has an equivalent mass EW of ion exchange groups of 600 g / eq or more and 2000 g / eq or less,
[0330] Among the dimensional changes of the electrolyte membrane caused by immersion in distilled water, the dimensional change in at least one of the X direction and the Y direction is 80% or more and less than 100%, and the dimensional change in the Z direction is 115% or more.
[0331] <Dimensional change rate caused by distilled water immersion>
[0332] A test electrolyte membrane having a moisture content of less than 1% was prepared, and the test electrolyte membrane was immersed in distilled water at 25° C. for 30 minutes. The dimensional change rates in the X direction, the Y direction orthogonal to the X direction, and the Z direction orthogonal to the X and Y directions on the surface of the test electrolyte membrane were calculated.
[0333] Dimension change rate (%) = {(dimension in a specific direction after immersion) / (dimension in a specific direction before immersion)}×100
[0334] Example
[0335] Hereinafter, the present embodiment will be described in more detail by way of examples, but the present embodiment is not limited to the following examples. It should be noted that the evaluation method and the measurement method used in the present embodiment are as follows.
[0336] <Equivalent mass EW>
[0337] About 0.02-0.10 g of electrolyte membrane was immersed in 50 mL of 25°C saturated NaCl aqueous solution (0.26 g / mL), and allowed to stand for 30 minutes while stirring. Then, phenolphthalein (manufactured by Wako Pure Chemical Industries, Ltd., special reagent grade) was used as an indicator, and 0.01 N sodium hydroxide aqueous solution (manufactured by Wako Pure Chemical Industries, Ltd., special reagent grade) was used for neutralization titration. After neutralization, the obtained Na-type ion exchange membrane was rinsed with pure water, vacuum dried and weighed. The equivalent amount of sodium hydroxide required for neutralization was recorded as M (mmol), and the mass of the Na-type ion exchange membrane was recorded as W (mg). The equivalent mass EW (g / eq) was calculated using the following formula.
[0338] Equivalent mass EW = (W / M) - 22
[0339] After repeating the above operation 5 times, the maximum value and the minimum value of the calculated 5 EW values were removed, and the arithmetic average of the three values was taken as the measurement result.
[0340] <Film thickness after stretching>
[0341] The stretched electrolyte membrane was left to stand in a thermostatic chamber at 23° C. and a relative humidity of 65% for 12 hours or more, and then measured using a contact-type film thickness meter (manufactured by Toyo Seiki Seisaku-sho, Ltd.).
[0342] <Flatness>
[0343] The flatness of the electrolyte membrane is evaluated by the ratio of the length along the membrane surface to the projected size of the membrane. The length along the membrane surface is obtained by the height-position curve of the membrane surface measured using a reading microscope. Specifically, the height of the membrane surface of a membrane cut into about 140 mm square is measured at 25 intervals of 5 mm in the X-axis direction. The height-position curve of the membrane surface is approximated by a spline function, and the length along the membrane surface is calculated by numerical calculation. The flatness index is calculated using the following formula and evaluated according to the following benchmarks.
[0344] Flatness index = length along the film surface / projection size of the film
[0345] A: less than 1.05
[0346] B: 1.05 or more and less than 1.1
[0347] C: 1.1 or more and less than 1.2
[0348] D: 1.2 or above
[0349] <Crack Area Ratio>
[0350] The crack area ratio is obtained by mapping the visible light transmittance, which is measured using an optical microscope equipped with an automatic base that can move in any X-axis direction and a Y-axis direction orthogonal to the X-axis and a visible light spectrophotometer "uSight-2000" (product name, manufactured by Technospex). The light focused to a diameter of 1 μm is moved in steps of 1 μm to map the visible light transmittance of the stretched film in a range of 75 mm in length and 50 mm in width. The wavelength range of the measured visible light is set to 450-700 nm. The ratio of the area of the mapped region with a transmittance of less than 10% to the total area is set as the crack area ratio (%).
[0351] <Piercing Strength>
[0352] The puncture strength was measured using a puncture strength tester "Puncture Strength Tester SPK-NDA1-A" (product name, manufactured by KATOTECH) for an electrolyte membrane placed at room temperature for more than 12 hours. The electrolyte membrane sandwiched between two metal plates with a circular hole of 10 mm in diameter was punctured at a speed of 2 mm / sec using a needle with a curvature radius of 0.5 mm. The puncture strength (kgf / μm) was calculated by dividing the maximum load (kgf) of the load-displacement curve by the thickness (μm) of the electrolyte membrane.
[0353] <Ion cluster diameter>
[0354] The ion cluster diameter is measured using small-angle X-ray scattering (SAXS). The electrolyte membrane is immersed in water at 25°C for 24 hours. While immersed in water, X-rays are incident from the membrane surface direction and the direction perpendicular to the membrane surface, and the transmitted scattered light is detected. The measurement uses a small-angle X-ray scattering measurement device "Nano Viewer" (manufactured by RIGAKU). For the small-angle area, the sample-detector distance is 841 mm, and the detector uses "PILATUS100K" (manufactured by RIGAKU). For the wide-angle area, the distance between the sample and the detector is 75 mm, and the detector uses an imaging plate. The measurement is performed and the two curves are merged to obtain scattering data for scattering angles in the range of 0.1°<scattering angle (2θ)<30°.
[0355] The sample was measured in a state of overlapping 7 images, and the exposure time in the small-angle area and wide-angle area measurements was set to 15 minutes. When acquiring data through a two-dimensional detector, the data is converted to one dimension using a reasonable method such as circular averaging. For the obtained SAXS curve, corrections derived from the detector such as the dark current correction of the detector and corrections for scattering caused by substances other than the sample (empty unit scattering correction) are implemented. When the influence of the X-ray beam shape on the SAXS curve (the influence of blurring) is large, the X-ray beam shape is also corrected (deblurring). For the one-dimensional SAXS curve obtained in this way, the ion cluster diameter is calculated according to the method described in Yasuhiro Hashimoto, Naoki Sakamoto, and Hideki Iijima, Collected Papers on Polymers, vol. 63, No. 3, pp. 166, 2006. That is, assuming that the ion cluster structure is represented by a core-shell rigid sphere with a particle size distribution, the SAXS curve of the scattering angle region dominated by the scattering of the ion clusters of the actual measured SAXS curve is fitted using the theoretical scattering formula based on the model, thereby obtaining the average cluster diameter (ion cluster diameter) and the number density of ion clusters. In this model, the core portion is equivalent to the ion cluster, and the core diameter becomes the ion cluster diameter. It should be noted that the shell is a hypothetical object, and the electron density of the shell is set to be the same as that of the matrix portion. In addition, the shell thickness here is set to 0.25nm. The theoretical scattering formula of the model used for fitting is shown in the following formula (A). In addition, the fitting range is set to 1.4<2θ<6.7°.
[0356] [Mathematical formula 2]
[0357]
[0358] Here,
[0359] q=4πsinθ / λ
[0360]
[0361]
[0362] α=(1+2η) 2 / (1-η) 4
[0363] β=-6η(1+η / 2) 2 / (1-η) 4
[0364] γ=1 / 2η(1+2η) 2 / (1-η) 4
[0365] A=2qa2
[0366] a2=a0+t
[0367]
[0368]
[0369]
[0370]
[0371]
[0372] In the above, C represents the device constant, N represents the cluster number density, η represents the core, in other words, the volume fraction of the ion cluster part and the imaginary shell around it when it is assumed to be a rigid sphere, θ represents the Bragg angle, λ represents the wavelength of the X-ray used, t represents the shell thickness, a0 represents the average ion cluster radius, Γ(x) represents the gamma function, and σ represents the standard deviation of the ion cluster radius (core radius). P(a) represents the distribution function of the core radius a, and here, it is assumed that the volume distribution of a follows the Gaussian distribution p(a). I b(q) represents the background scattering including scattering from excess water and thermal diffuse scattering during measurement, and is assumed to be a constant. When fitting, among the above parameters, N, η, a0, σ, I b(q) It is set as a variable parameter. It should be noted that in this specification, the ion cluster diameter refers to the average diameter (2a0) of the ion clusters.
[0373] <Orientation Parameters>
[0374] The in-plane orientation parameter and out-of-plane orientation parameter of the electrolyte membrane are obtained by approximating the azimuthal intensity distribution I(φ) of the peak derived from the ion cluster in the two-dimensional small-angle scattering measured by the above method using the orientation function shown in the following formula.
[0375] [Mathematical formula 3]
[0376]
[0377] Here, Q is a constant, φ is the azimuth angle, and q is the orientation parameter.
[0378] When determining the film in-plane orientation parameter, the X direction is set to φ = 0. Therefore, if the ion clusters are completely oriented along the X direction, q is 1, whereas if they are completely oriented along the Y direction, q is -1. On the other hand, q is 0 in the case of random orientation.
[0379] When obtaining the out-of-plane orientation parameter of the film, the normal direction of the film is set to φ = 0. Therefore, if the ion clusters are completely oriented along the normal direction, q is 1, while if they are completely oriented along the film surface direction, q is -1. On the other hand, q is 0 when randomly oriented.
[0380] <Long crystallization period>
[0381] The crystal long period is calculated as follows: In the one-dimensional SAXS curve obtained by the above method, the scattering vector is 0.1 to 1.0 nm. -1 The position of the periodic peak originating from the electron density difference between the crystal and the amorphous phase generated within the range of is determined using the Bragg equation.
[0382] On the other hand, the peak intensity is defined as the ratio of the difference between the peak top intensity and the baseline intensity to the baseline intensity. It should be noted that if no peak is detected, it is regarded as no intensity difference is detected and is recorded as "-".
[0383] <Dimensional change rate caused by immersion in 2M sulfuric acid aqueous solution>
[0384] The electrolyte membrane was dried at a temperature below 50°C and under reduced pressure for 2 hours, and after the moisture content was adjusted to less than 1% by mass, it was cut into a square with a single side of 7 cm to prepare a test electrolyte membrane. The test electrolyte membrane was immersed in a 2M sulfuric acid aqueous solution at 25°C for 30 minutes. Using a reading microscope "D2XY-KSH" (product name, made by Nippon Koki Seisakusho), the dimensions of the test electrolyte membrane in the X and Y directions after immersion were measured, and the dimensional change rate was calculated using the following formula. It should be noted that the X direction is an optional direction on the membrane surface, and the Y direction refers to the direction perpendicular to the X direction on the membrane surface.
[0385] Dimension change rate (%) = {(dimension in a specific direction after immersion) / (dimension in a specific direction before immersion)}×100
[0386] Tables 1 and 2 show the obtained dimensional change rates.
[0387] <Dimensional change rate caused by distilled water immersion>
[0388] The electrolyte membrane was dried at a temperature below 50°C and under reduced pressure for 2 hours, and after the moisture content was adjusted to below 1%, it was cut into a square with a single side of 7 cm to prepare a test electrolyte membrane. The test electrolyte membrane was immersed in distilled water at 25°C for 30 minutes. Using a reading microscope "D2XY-KSH" (product name, made by Nippon Koki Manufacturing Co., Ltd.), the dimensions of the test electrolyte membrane in the X, Y and Z directions after immersion were measured, and the dimensional change rate was calculated using the following formula. It should be noted that the X direction is an optional direction on the membrane surface, and the Y direction refers to the direction perpendicular to the X direction on the membrane surface. The Z direction refers to the direction orthogonal to the X direction and the Y direction.
[0389] Dimension change rate (%) = {(dimension in a specific direction after immersion) / (dimension in a specific direction before immersion)}×100
[0390] Tables 1 and 2 show the obtained dimensional change rates.
[0391] <Moisture content>
[0392] The electrolyte membrane was cut into 5 cm×5 cm pieces, and the initial weight was measured using a precision balance. Thereafter, the weight after drying was measured using a halogen moisture meter “HX204” (product name, manufactured by Mettler Toledo Corporation) under the following measurement conditions.
[0393] Measurement conditions
[0394] Drying process: slow
[0395] Light time: 3.00 minutes
[0396] Drying temperature: 160℃
[0397] Close standard: 1mg / 50 seconds
[0398] Moisture content (%) = {(initial weight - weight after drying) / (weight after drying)} × 100
[0399] <Redox flow battery evaluation (1)>
[0400] In the redox flow battery evaluation (1), a unit consisting of a VITON rubber gasket, a Teflon (registered trademark) flow path frame, a graphite separator, and a stainless steel bottom plate was used. The electrolyte membrane was used by cutting the electrolyte prepared in the embodiments and comparative examples into 50×80 mm. The gasket adjusted the membrane thickness in such a way that the compression rate of the electrode (the ratio of thickness before and after compression) reached 75%. The electrode was used by cutting the carbon fiber nonwoven fabric "SIGRACELL GFA6EA" (product name, manufactured by SGL CARBON) into 33×30 mm.
[0401] Combine the two electrodes, electrolyte membrane and unit components in the prescribed order and tighten them with stainless steel bolts at the prescribed torque. Connect the assembled unit to the electrolyte circulation device consisting of an electrolyte tank and a liquid delivery pump. Add 30 mL of vanadium sulfuric acid solution with a vanadium ion concentration of 1.5 M, a vanadium ion valence of 3.5, and a sulfate ion concentration of 4.5 M to the electrolyte tank, and circulate at a flow rate of 100 mL / min. The charge and discharge test uses a constant current method using a potentiostat "VSP" (product name, manufactured by BioLogic). The voltage range is set to 1.00-1.55 V and the current density is set to 80 mA / cm 2 .
[0402] (Self-discharge)
[0403] The same setting as in the redox flow battery evaluation (1) was followed by charging to 1.55 V, then opening the circuit and measuring the cell voltage every hour. The time taken for the cell voltage to fall below 1.00 V was evaluated according to the following criteria.
[0404] A: More than 250 hours.
[0405] B: 200 hours or more and less than 250 hours.
[0406] C: 150 hours or more and less than 200 hours.
[0407] D: Less than 150 hours.
[0408] (Unit resistance)
[0409] The average voltage V during charge and discharge is calculated by the following formula: c and V d The resistance was determined. The obtained results are shown in Tables 1 and 2.
[0410] Unit resistance = (V c -V d ) / (2×0.08)(Ωcm 2 )
[0411] (Liquid Movement)
[0412] The charge and discharge in the range of 1.00 to 1.55 V was defined as one cycle. After 200 cycles of evaluation, the electrolyte amount in the electrolyte tank was evaluated, and the difference (mL) between the electrolyte amounts on the negative side and the positive side is recorded in Tables 1 and 2.
[0413] (Deflection of membrane)
[0414] After the redox flow battery evaluation (1) was continued for 200 cycles, the cell was disassembled, the gasket and the electrolyte membrane were taken out, and evaluation was performed from the following viewpoints.
[0415] A: The gasket and the electrolyte membrane did not deflect.
[0416] B: The electrolyte membrane swells and deflects by 0.5 mm or more from the gasket surface.
[0417] C: The electrolyte membrane swells and deflects by 1.0 mm or more from the gasket surface.
[0418] D: During the evaluation, cracks occurred in the electrolyte membrane.
[0419] (Film cracking)
[0420] The cross section of the electrolyte membrane after the redox flow battery evaluation was continuously evaluated for 200 cycles was observed using a scanning electron microscope "SU8010" (product name, manufactured by Hitachi HITECH Co., Ltd.), and evaluated from the following viewpoints.
[0421] A: No cracks occurred on the cross section.
[0422] B: A crack extending in the film surface direction occurs in the cross section.
[0423] C: 2 to 3 cracks extending in the film surface direction are generated in the cross section.
[0424] D: Three or more cracks extending in the film surface direction are generated in the cross section.
[0425] (Current efficiency)
[0426] The current efficiency was determined by dividing the discharge capacity by the charge capacity at 200 charge and discharge cycles.
[0427] <Perfluorocarbon polymer>
[0428] In this embodiment, perfluorocarbon polymers having the following two structures were used.
[0429] Perfluorocarbon polymer comprising the structure represented by the following formula (P1)
[0430] -[CF2CF2]-[CF2-CF(-O-CF2CF2-SO3H)]- (P1)
[0431] Perfluorocarbon polymer containing the structure represented by the following formula (P2)
[0432] -[CF2CF2]-[CF2-CF(-O-CF2CFCF3-O-CF2CF2-SO3H)]- (P2)
[0433] (Example 1)
[0434] An intermittent biaxial stretching machine "IMC-1AA6" (product name, manufactured by Imoto Manufacturing Co., Ltd.) is used to stretch a raw film with a thickness of 100 μm formed by a perfluorocarbon polymer (polymer structure: formula (P1), equivalent mass EW = 950 g / eq) by simultaneous biaxial stretching. The raw film cut into 92.5 mm in the orthogonal X and Y directions is gripped by the stretching machine in such a way that the chuck spacing in the X and Y directions reaches 72.5 mm. After 3 minutes from the time when the temperature of the heating chamber of the stretching machine reaches 140°C, simultaneous biaxial stretching is started at a stretching speed of 100 mm / min. After the chuck spacing in the X and Y directions reaches 145 mm, the stretching is stopped, and the heating chamber is immediately opened while the film is gripped by the chucks to start cooling. At the same time, the chuck spacing is narrowed by 0.7 mm in such a way that the relaxation rate in the X and Y directions reaches 0.5%. After the membrane was cooled to room temperature, it was removed from the chuck to obtain a biaxially stretched electrolyte membrane having a stretching ratio of 2.0 in the X direction and the Y direction.
[0435] (Example 2)
[0436] A biaxially stretched electrolyte membrane was produced in the same manner as in Example 1 except that the thickness of the raw material film was 150 μm and the stretching ratios in the X and Y directions were 2.5.
[0437] (Example 3)
[0438] A biaxially stretched electrolyte membrane was produced in the same manner as in Example 1 except that the thickness of the raw material film was 70 μm and the stretching ratios in the X direction and the Y direction were 2.9 and 1.0, respectively.
[0439] (Example 4)
[0440] A biaxially stretched electrolyte membrane was produced in the same manner as in Example 1 except that the thickness of the raw material film was 180 μm and the stretching ratios in the X direction and the Y direction were 2.9 and 2.5, respectively.
[0441] (Example 5)
[0442] A biaxially stretched electrolyte membrane was produced in the same manner as in Example 1 except that the thickness of the raw material film was 210 μm, the stretching ratios in the X and Y directions were 2.9, and the relaxation rate during cooling was 1.0%.
[0443] (Example 6)
[0444] A biaxially stretched electrolyte membrane was produced in the same manner as in Example 1 except that the equivalent weight EW of the perfluorocarbon polymer was 1150 g / eq, the thickness of the raw film was 80 μm, and the stretching ratios in the X and Y directions were 1.8.
[0445] (Example 7)
[0446] A biaxially stretched electrolyte membrane was produced in the same manner as in Example 6 except that the thickness of the raw material film was set to 65 μm.
[0447] (Example 8)
[0448] A biaxially stretched electrolyte membrane was produced in the same manner as in Example 1 except that the equivalent weight EW of the perfluorocarbon polymer was changed to 700 g / eq.
[0449] (Example 9)
[0450] The polymer was changed to a perfluorocarbon polymer (polymer structure: formula (P2), equivalent mass EW = 1100 g / eq), the thickness of the raw material membrane was set to 150 μm, the stretching ratio in the X and Y directions was set to 2.5, and the stretching temperature was set to 100°C. Except for this, a biaxially stretched electrolyte membrane was prepared in the same manner as in Example 1.
[0451] (Example 10)
[0452] A biaxially stretched electrolyte membrane was produced in the same manner as in Example 9 except that the thickness of the raw material film was 200 μm and the stretching ratios in the X direction and the Y direction were 3.2 and 2.5, respectively.
[0453] (Example 11)
[0454] A biaxially stretched electrolyte membrane was produced in the same manner as in Example 9 except that the thickness of the raw material film was 420 μm and the stretching ratios in the X direction and the Y direction were each 5.2.
[0455] (Example 12)
[0456] The electrolyte membrane was biaxially stretched in the same manner as in Example 1 except that the thickness of the raw material film was 180 μm and the stretching ratios in the X and Y directions were 2.9 and 2.5, respectively. The obtained membrane was fixed to a metal frame and heat treated at 140° C. for 5 minutes to produce a biaxially stretched electrolyte membrane.
[0457] (Example 13)
[0458] A biaxially stretched electrolyte membrane was produced in the same manner as in Example 12 except that the thickness of the raw material film was 210 μm, the stretching ratios in the X and Y directions were 2.9, and the relaxation rate during cooling was 1.0%.
[0459] (Example 14)
[0460] The electrolyte membrane was biaxially stretched in the same manner as in Example 9 except that the thickness of the raw material film was 200 μm and the stretching ratios in the X and Y directions were 3.2 and 2.5, respectively. Furthermore, the obtained membrane was fixed to a metal frame and heat treated at 100° C. for 5 minutes to produce a biaxially stretched electrolyte membrane.
[0461] (Example 15)
[0462] A biaxially stretched electrolyte membrane was produced in the same manner as in Example 14 except that the thickness of the raw material film was 420 μm and the stretching ratios in the X direction and the Y direction were each 5.2.
[0463] (Example 16)
[0464] A biaxially stretched electrolyte membrane was produced in the same manner as in Example 13 except that the relaxation rate during cooling was set to 0.5%.
[0465] (Example 17)
[0466] A biaxially stretched electrolyte membrane was produced in the same manner as in Example 13 except that the relaxation rate during cooling was set to 0.2%.
[0467] (Example 18)
[0468] A biaxially stretched electrolyte membrane was produced in the same manner as in Example 13 except that the polymer was changed to a perfluorocarbon polymer (polymer structure: formula (P1), equivalent mass EW=750 g / eq).
[0469] (Example 19)
[0470] After preparing a biaxially stretched electrolyte membrane in the same manner as in Example 18, the electrolyte membrane was immersed in a 10 mass % polyvinylpyridine aqueous solution for 10 minutes, washed with water, and dried overnight to prepare an electrolyte membrane.
[0471] (Example 20)
[0472] After preparing a biaxially stretched electrolyte membrane in the same manner as in Example 18, the electrolyte membrane was immersed in a 0.1 mass % dodecyltrimethylammonium chloride aqueous solution for 10 minutes, washed with water, and dried overnight to prepare an electrolyte membrane.
[0473] (Example 21)
[0474] A biaxially stretched electrolyte membrane was produced in the same manner as in Example 13 except that the relaxation rate during cooling was set to 0%.
[0475] (Comparative Example 1)
[0476] An electrolyte membrane was produced in the same manner as in Example 1 except that the raw material membrane was changed to a raw material membrane having a thickness of 25 μm and formed of a perfluorocarbon polymer (polymer structure: formula (P1), equivalent mass EW=750 g / eq) and biaxial stretching was not performed.
[0477] (Comparative Example 2)
[0478] A biaxially stretched electrolyte membrane was produced in the same manner as in Example 1 except that the equivalent weight EW of the perfluorocarbon polymer was 750 g / eq, the stretching ratios in the X and Y directions were 2.0, and the relaxation rate during cooling was 0%.
[0479] (Comparative Example 3)
[0480] A biaxially stretched electrolyte membrane was produced in the same manner as in Example 1 except that the thickness of the raw material film was 400 μm, the stretching ratios in the X and Y directions were 4.0, and the relaxation rate during cooling was 0%.
[0481] (Comparative Example 4)
[0482] The polymer structure of the perfluorocarbon polymer is set to formula (P2), the equivalent mass EW is set to 1100 g / eq, the thickness of the raw material film is set to 200 μm, the stretching ratios in the X direction and the Y direction are set to 3.2 and 2.5 respectively, the stretching temperature is set to 100°C, and the relaxation rate during the cooling process is set to 0%. Except for this, the same operations are performed as in Example 1 to prepare a biaxially stretched electrolyte membrane.
[0483] [Table 1]
[0484]
[0485] [Table 2]
[0486]
[0487] (Example 22)
[0488] <Production of Carbon Foam>
[0489] As a material for carbon foam, melamine resin foam (size: 400mm×400mm×40mm) was prepared and introduced into a heat treatment furnace under a compressive load of 280Pa applied by carrying a graphite plate (size: 400mm×400mm×16mm). Next, the furnace was decompressed and exhausted by a vacuum pump so that the vacuum degree in the furnace was less than 1Pa. Next, nitrogen was supplied to the furnace at a flow rate of 2L / min while decompressing and exhausting, while the temperature in the furnace was raised to 400°C at 2.5°C / min, and from 400°C to 800°C at 5°C / min. At the moment when the temperature in the furnace reached 800°C, the degree of decompression in the furnace was about 700Pa. At the moment when the temperature in the furnace reached 800°C, the supply of nitrogen was stopped, and the temperature was raised to a heat treatment temperature of 2000°C at a heating rate of 5°C / min, and maintained for 2 hours to carbonize the melamine resin foam. When the temperature in the furnace reaches 2000°C, the degree of reduced pressure in the furnace is less than 10Pa. Thereafter, after the temperature in the furnace is lowered to room temperature, the vacuum pump is stopped and the carbonized melamine resin foam is taken out of the furnace. Next, the obtained carbon foam is heat-treated at 600°C for 2 hours under a flow of dry air to obtain a carbon foam with an oxidized surface. It should be noted that the dry air flow rate is set to 1L / min. The carbon foam of Example 22 is prepared in this way. When the obtained carbon foam is observed using SEM, it can be confirmed that it has a linear portion and a bonding portion that connects the linear portion, and the carbon portion is a three-dimensional continuous structure. Figure 2 ] A SEM image of the carbon foam obtained in Example 22 is shown in FIG. Figure 2 , (a) is a SEM image of a cross section of the carbon foam, and (b) is a SEM image of a surface of the carbon foam.
[0490] <Measurement of Average Fiber Diameter>
[0491] The surface of any part of the obtained carbon foam was analyzed by scanning electron microscope (SEM) images at a magnification of 10,000 times to obtain the thickness of the fibrous carbon constituting the observed carbon foam, assuming that the cross-sectional shape was circular, and the fiber diameter was determined by taking the number average of the fiber diameters measured at any 20 locations as the average fiber diameter.
[0492] <Structural analysis based on X-ray CT>
[0493] The carbon foam was subjected to structural analysis by X-ray CT. Specifically, in order to facilitate the taking of X-ray images, a test piece was taken after chemical copper plating, and the structure of the sample was analyzed using a high-resolution 3D X-ray microscope "nano3DX" (product name, manufactured by RIGAKU). The specific chemical plating conditions and X-ray CT analysis conditions are as follows.
[0494] (Electroless Plating Conditions)
[0495] The sample was immersed in "OPC CONDICLEAN MA" (product name, manufactured by Okuno Pharmaceutical Co., Ltd., diluted with distilled water to a concentration of 100 mL / L) at 70°C for 5 minutes, and then washed with distilled water for 1 minute. Next, it was immersed in "OPC PREDIP 49L" (product name, manufactured by Okuno Pharmaceutical Co., Ltd., diluted with distilled water to a concentration of 10 mL / L, and 1.5 mL / L of 98% by mass sulfuric acid was added) at 70°C for 2 minutes, and then washed with distilled water for 1 minute. Next, it was immersed in a solution obtained by mixing "OPC Inducer 50AM" (product name, manufactured by Okuno Pharmaceutical Co., Ltd., diluted with distilled water to a concentration of 100 mL / L) and "OPC inducer 50CM" (product name, manufactured by Okuno Pharmaceutical Co., Ltd., diluted with distilled water to a concentration of 100 mL / L) at a volume ratio of 1:1 at 45°C for 5 minutes, and then washed with distilled water for 1 minute. Next, after immersing in "OPC-150cryster MU" (product name, made by Okuno Pharmaceutical Industry Co., Ltd., diluted with distilled water in a concentration of 150mL / L) for 5 minutes at room temperature, wash with distilled water for 1 minute. Next, immerse in "OPC-BSM" (product name, made by Okuno Pharmaceutical Industry Co., Ltd., diluted with distilled water in a concentration of 125mL / L) for 5 minutes at room temperature. Next, in a solution obtained by mixing "Chemical Copper 500A" (product name, made by Okuno Pharmaceutical Industry Co., Ltd., diluted with distilled water in a concentration of 250mL / L) and "Chemical Copper 500B" (product name, made by Okuno Pharmaceutical Industry Co., Ltd., diluted with distilled water in a concentration of 250mL / L) in 1:1, immerse at room temperature for 10 minutes, and wash with distilled water for 5 minutes. Thereafter, vacuum drying was performed at 90°C for 12 hours to dry the water.
[0496] (X-ray conditions)
[0497] X-ray target: Cu
[0498] X-ray tube voltage: 40kV
[0499] X-ray tube current: 30mA
[0500] (Shooting conditions)
[0501] Number of projections: 1500
[0502] Rotation angle: 180°
[0503] Exposure time: 20 seconds / frame
[0504] Spatial resolution: 0.54 μm / pixel
[0505] (X-ray CT analysis conditions)
[0506] The obtained three-dimensional image was processed with a median filter using adjacent 1 pixel, and binarized using Otsu's algorithm. Next, the software "simpleware's Centerline editor (Ver.7)" (product name, manufactured by JSOL) was used with default settings to remove lines below 2.16 μm as noise, and an image with line and knot detection was formed within a measurement field of 300 μm × 300 μm × 300 μm. The number of junctions and linear parts was detected using this image, and the ratio R (N l / N m ) and the density of the junction (N n / mm 3 ).
[0507] Figure 3 ] An X-ray CT analysis image of the carbon foam obtained in Example 22 is shown in FIG. Figure 4 ] X-ray CT analysis images of the carbon foam obtained in Example 22 at other angles are shown. Figure 5 Shown in the Figure 3 The X-ray CT analysis image of the carbon foam shown is an image after image processing for line and knot detection.
[0508] <Redox flow battery evaluation (2)>
[0509] In the redox flow battery evaluation (2), a unit consisting of a VITON rubber gasket, a Teflon (registered trademark) flow path frame, a graphite separator, and a stainless steel bottom plate was used. A comb-tooth-shaped flow path was provided parallel to the short side in the 33×30 mm portion of the graphite separator opposite to the electrode. The rib width, groove width, and groove depth of the flow path were set to 1 mm, 1 mm, and 1.5 mm, respectively. The electrolyte membrane used was the membrane prepared in Example 4. The gasket adjusted the membrane thickness in such a way that the compression rate of the electrode reached 70%.
[0510] Combine the membrane cut into 50×80 mm, 2 pieces of carbon foam cut into 33×30 mm, and the unit components in the prescribed order and tighten them with stainless steel bolts at the prescribed torque. Connect the assembled unit to the electrolyte circulation device consisting of an electrolyte tank and a liquid delivery pump. Add 30 ml of vanadium sulfuric acid solution with a vanadium ion concentration of 1.5 M, a vanadium ion valence of 3.5, and a sulfate ion concentration of 4.5 M to the electrolyte tank, and circulate at a flow rate of 100 ml / min. The charge and discharge test uses a constant current method using a potentiostat "VSP" (product name, manufactured by BioLogic). The voltage range is set to 1.00-1.55 V and the current density is set to 80 mA / cm 2 The cell resistance is calculated from the average voltages Vc and Vd during charge and discharge using the following equation.
[0511] Unit resistance (Ωcm 2 )=(Vc-Vd) / (2×0.08)
[0512] In addition, the current density is 80 mA / cm 2 The current efficiency is calculated by the discharge amount relative to the charge amount at that time.
[0513] (Example 23)
[0514] Prepare melamine resin foam (size: 400mm×400mm×20mm), place a 0.6mm thick SUS plate as a spacer around the sample, clamp it from top to bottom with a 10mm thick graphite plate, and introduce it into a vacuum heat press "KVHC-II" (product name, made by Kitagawa Seiki Co., Ltd.). Except for this, use the same conditions as in Example 22 to make carbon foam.
[0515] In addition, the evaluation was performed under the same conditions as in Example 22.
[0516] (Example 24)
[0517] A biaxially stretched electrolyte membrane was prepared in the same manner as in Example 9 except that the thickness of the raw film was 400 μm and the stretching ratios in the X and Y directions were each 4.5. A carbon foam was prepared in the same manner as in Example 23 and evaluated under the same conditions as in Example 22 except that the carbon foam was produced in the same manner as in Example 23.
[0518] (Example 25)
[0519] A biaxially stretched electrolyte membrane was prepared in the same manner as in Example 9 except that the thickness of the raw film was 420 μm and the stretching ratios in the X and Y directions were each 4.8. A carbon foam was prepared in the same manner as in Example 23 and evaluated under the same conditions as in Example 22 except that the carbon foam was produced in the same manner as in Example 23.
[0520] (Example 26)
[0521] A biaxially stretched electrolyte membrane was prepared in the same manner as in Example 9 except that the thickness of the raw film was 400 μm and the stretching ratios in the X and Y directions were each 5.2. A carbon foam was prepared in the same manner as in Example 23 and evaluated under the same conditions as in Example 22 except that the carbon foam was produced in the same manner as in Example 23.
[0522] (Example 27)
[0523] A biaxially stretched electrolyte membrane was prepared in the same manner as in Example 9 except that the thickness of the raw film was 130 μm and the stretching ratios in the X and Y directions were each 2.9. A carbon foam was prepared in the same manner as in Example 23 and evaluated under the same conditions as in Example 22 except that the carbon foam was produced in the same manner as in Example 23.
[0524] (Example 28)
[0525] Evaluation was performed under the same conditions as in Example 22 using a biaxially stretched film produced in the same manner as in Example 12 and a carbon foam produced in the same manner as in Example 22.
[0526] (Example 29)
[0527] Evaluation was performed under the same conditions as in Example 22 using the biaxially stretched film produced in the same manner as in Example 12 and the carbon foam produced in the same manner as in Example 23.
[0528] (Example 30)
[0529] A biaxially stretched electrolyte membrane was prepared in the same manner as in Example 14 except that the thickness of the raw film was 400 μm and the stretching ratios in the X and Y directions were each 5.2. A carbon foam was prepared in the same manner as in Example 23 and evaluated under the same conditions as in Example 22 except that the carbon foam was produced in the same manner as in Example 23.
[0530] (Example 31)
[0531] Evaluation was performed under the same conditions as in Example 22, except that a biaxially stretched electrolyte membrane was produced in the same manner as in Example 18 and a carbon foam was produced in the same manner as in Example 23.
[0532] (Example 32)
[0533] Evaluation was performed under the same conditions as in Example 22, except that a biaxially stretched electrolyte membrane was produced in the same manner as in Example 19 and a carbon foam was produced in the same manner as in Example 23.
[0534] [Table 3]
[0535]
[0536] As described above, based on the comparison between the embodiments and the comparative examples, it can be seen that by setting the dimensional change rate of the electrolyte membrane caused by immersion in a 2M sulfuric acid aqueous solution or the dimensional change rate of the electrolyte membrane caused by immersion in distilled water to a specified range, an electrolyte membrane for a redox flow battery with suppressed self-discharge and excellent battery performance can be obtained.
[0537] This application is based on Japanese patent application (Japanese Patent Application No. 2019-042876) filed on March 8, 2019 and Japanese patent application (Japanese Patent Application No. 2019-167421) filed on September 13, 2019, the contents of which are incorporated herein by reference.
Claims
1. An electrolyte membrane for a redox flow battery, comprising a perfluorocarbon polymer having ion exchange groups, The perfluorocarbon polymer has an equivalent mass EW of ion exchange groups of 600 g / eq or more and 2000 g / eq or less, The crack area ratio in the electrolyte membrane is 0.1% or more and 1.5% or less, The electrolyte membrane has a dimensional change rate of 80% or more and less than 100% in at least one of the X direction and the Y direction among the following dimensional changes caused by immersion in a 2M sulfuric acid aqueous solution, Dimensional change rate caused by immersion in 2M sulfuric acid aqueous solution: A test electrolyte membrane having a water content of 1% or less was prepared, and the test electrolyte membrane was immersed in a 2M sulfuric acid aqueous solution at 25° C. for 30 minutes, and the dimensional change rate in the X direction and the Y direction orthogonal to the X direction on the surface of the test electrolyte membrane was calculated by the following formula: Dimensional change rate (%) = {(dimension in a specific direction after immersion) / (dimension in a specific direction before immersion)}×100, The electrolyte membrane is manufactured by the following method: the method includes a process of stretching a raw material membrane containing a perfluorocarbon polymer having ion exchange groups, and a process of performing a relaxation treatment during cooling after the stretching process, wherein the area stretching ratio obtained by multiplying the stretching ratio in the X-axis direction by the stretching ratio in the Y-axis direction is greater than 2.2 times and less than 50 times, and the relaxation rate is greater than 0.1% and less than 5.0%.
2. The electrolyte membrane according to claim 1, wherein Among the dimensional changes of the electrolyte membrane caused by immersion in a 2M sulfuric acid aqueous solution, the dimensional change rate in at least one of the X direction and the Y direction is 90% or more and 99.5% or less.
3. An electrolyte membrane for a redox flow battery, comprising a perfluorocarbon polymer having ion exchange groups, The perfluorocarbon polymer has an equivalent mass EW of ion exchange groups of 600 g / eq or more and 2000 g / eq or less, The crack area ratio in the electrolyte membrane is 0.1% or more and 1.5% or less, Among the following dimensional changes of the electrolyte membrane caused by immersion in distilled water, the dimensional change rate in at least one of the X direction and the Y direction is 80% or more and less than 100%, and the dimensional change rate in the Z direction is 115% or more, Dimensional change rate caused by distilled water immersion: A test electrolyte membrane having a water content of 1% or less is prepared, the test electrolyte membrane is immersed in distilled water at 25° C. for 30 minutes, and the dimensional change rates in the X direction, the Y direction orthogonal to the X direction, and the Z direction orthogonal to the X direction and the Y direction on the surface of the test electrolyte membrane are calculated. Dimensional change rate (%) = {(dimension in a specific direction after immersion) / (dimension in a specific direction before immersion)}×100, The electrolyte membrane is manufactured by the following method: the method includes a step of stretching a raw material membrane containing a perfluorocarbon polymer having an ion-exchange group, and a step of performing a relaxation treatment during the cooling process after the stretching step, wherein the area stretching ratio obtained by multiplying the stretching ratio in the X-axis direction by the stretching ratio in the Y-axis direction is 2.2 times or more and 50 times or less, and the relaxation ratio is 0.1% or more and 5.0% or less.
4. The electrolyte membrane according to claim 3, wherein Among the dimensional change rates of the electrolyte membrane caused by immersion in distilled water, the dimensional change rate in at least one of the X direction and the Y direction is 90% or more and 99.5% or less, and the dimensional change rate in the Z direction is 160% or less.
5. The electrolyte membrane according to any one of claims 1 to 4, wherein The crack area ratio in the electrolyte membrane is 0.1% or more and 1.0% or less.
6. The electrolyte membrane according to any one of claims 1 to 4, wherein The perfluorocarbon polymer contains the structure represented by the following formula (1), -[CF2-CX 1 X 2 ] a -[CF2-CF(-O-(CF2-CF(CF2X 3 )) b -O c -(CFR 1 ) d -(CFR 2 ) e -(CF2) f -X 4 )] g -(1) In formula (1), X 1 , X 2 and X 3 are each independently a halogen atom or a perfluoroalkyl group having 1 to 3 carbon atoms; X 4 is a -COOZ group, -SO3Z group, -PO3Z2 group or -PO3HZ group; Z is a hydrogen atom, an alkali metal atom, an alkaline earth metal atom, NH4, NH3R 11 , NH2R 11 R 12 , NHR 11 R 12 R 13 or NR 11 R 12 R 13 R 14 ; R 11 , R 12 , R 13 and R 14 are each independently an alkyl group or an aryl group; R 1 and R 2 are each independently a halogen atom, a perfluoroalkyl group having 1 to 10 carbon atoms or a fluorochloroalkyl group having 1 to 10 carbon atoms; a and g are numbers satisfying 0 ≤ a < 1, 0 < g ≤ 1 and a + g = 1; b is an integer from 0 to 8; c is 0 or 1; d, e and f are each independently an integer from 0 to 6, provided that d, e and f are not simultaneously 0.
7. The electrolyte membrane according to any one of claims 1 to 4, wherein The perfluorocarbon polymer contains a repeating unit represented by -[CF2CF2]- and a repeating unit derived from a compound represented by the following formula (3), (4-1) or (4-2), CF2=CF(-O-(CF2CFXO) n -[A]) (3) In formula (3), X is F or a perfluoroalkyl group having 1 to 3 carbon atoms, n is an integer of 0 to 5, and [A] is (CF2) m -SO3H, m represents an integer of 0 to 6, wherein n and m are not 0 at the same time, CF2=CF-O-(CF2) P -CFX(-O-(CF2) K -SO3H) (4-1) CF2=CF-O-(CF2) P -CFX(-(CF2) L -O-(CF2) m -SO3H) (4-2) In formulas (4-1) and (4-2), X is a perfluoroalkyl group having 1 to 3 carbon atoms, P is an integer of 0 to 12, K is an integer of 1 to 5, L is an integer of 1 to 5, m is an integer of 0 to 6, wherein K and L are optionally the same or different, and P, K, and L are not simultaneously 0.
8. The electrolyte membrane according to any one of claims 1 to 4, wherein The perfluorocarbon polymer contains the structure represented by the following formula (2), -[CF2CF2] a -[CF2-CF(-O-(CF2) m -SO3H)] g -(2) In formula (2), a and g are numbers satisfying 0 ≤ a < 1 and 0 < g ≤ 1, and a + g = 1; m is an integer of 1 to 6.
9. The electrolyte membrane according to any one of claims 1 to 4, wherein The value of the melt flow index (MFI) of the perfluorocarbon polymer measured under the measurement conditions of a temperature of 270 °C and a load of 2160 g according to ASTM: D1238 is 0.05 g / 10 minutes or more and 50 g / 10 minutes or less.
10. The electrolyte membrane according to any one of claims 1 to 4, wherein The diameter of the ionic clusters in the direction perpendicular to the membrane surface of the electrolyte membrane measured by small-angle X-ray scattering is 3.0 nm or more.
11. The electrolyte membrane according to any one of claims 1 to 4, wherein The peak intensity of the crystalline long period of the electrolyte membrane measured by small-angle X-ray scattering is 0.5 or less.
12. The electrolyte membrane according to any one of claims 1 to 4, wherein The puncture strength of the electrolyte membrane based on the following puncture strength test is 0.01 kgf / μm or more, Puncture strength test: For the electrolyte membrane placed at room temperature for 12 hours or more, a needle with a curvature radius of 0.5 mm is used to pierce the electrolyte membrane clamped by two metal plates with a circular hole of 10 mm in diameter at a speed of 2 mm / sec. The value obtained by dividing the maximum load of the load-displacement curve in kgf by the thickness of the electrolyte membrane in μm is recorded as the puncture strength.
13. The electrolyte membrane according to any one of claims 1 to 4, wherein At least one surface of the electrolyte membrane is covered with an anion-exchangeable compound.
14. The electrolyte membrane according to claim 13, wherein The anion-exchangeable compound has a tertiary amino group or a quaternary ammonium group.
15. A redox flow battery, which includes an electrolytic cell, and the electrolytic cell includes: a positive electrode unit chamber containing a positive electrode formed of a carbon electrode, a negative electrode unit chamber containing a negative electrode formed of a carbon electrode, and an electrolyte membrane serving as a diaphragm for isolating and separating the positive electrode unit chamber from the negative electrode unit chamber, The positive electrode unit chamber includes: a positive electrode electrolyte containing an active material, The negative electrode unit chamber comprises: a negative electrode electrolyte containing an active material, The electrolyte membrane is the electrolyte membrane according to any one of claims 1 to 14.
16. The redox flow battery according to claim 15, wherein: The positive electrode electrolyte and the negative electrode electrolyte contain vanadium ions.
17. The redox flow battery according to claim 15 or 16, wherein: The carbon electrode has continuous gaps, The carbon electrode contains fibrous carbon, The fibrous carbon has an average fiber diameter of 0.1 to 5.0 μm.
18. The redox flow battery according to claim 17, wherein: The carbon electrode is a three-dimensional continuous carbon structure.
19. The redox flow battery according to claim 17, wherein: The carbon electrode is a carbon foam having a linear portion and a bonding portion bonding the linear portions.
20. The redox flow battery according to claim 19, wherein: The carbon foam has a ratio of the number of linear portions to the number of bonding portions of 1.2 to 1.
7.
21. The redox flow battery according to claim 19 or 20, wherein: In at least a portion of the carbon foam, the density of the bonding portions is 15,000 / mm 3 above.
22. The redox flow battery according to claim 19 or 20, wherein: The carbon foam has a carbon content of 51% by mass or more as determined by fluorescent X-ray measurement.
23. The redox flow battery according to claim 19 or 20, wherein: The carbon foam has a porosity of 50 volume % or more.
24. A method for manufacturing an electrolyte membrane for a redox flow battery, comprising: a step of stretching a raw material film comprising a perfluorocarbon polymer having an ion exchange group, and After the stretching step, a relaxation step is performed during cooling. The area stretching ratio obtained by multiplying the stretching ratio in the X-axis direction by the stretching ratio in the Y-axis direction is 2.2 to 50 times, and the relaxation rate is 0.1 to 5.0%. The perfluorocarbon polymer has an equivalent mass EW of ion exchange groups of 600 g / eq or more and 2000 g / eq or less, The crack area ratio in the electrolyte membrane is 0.1% or more and 1.5% or less, The electrolyte membrane has a dimensional change rate of 80% or more and less than 100% in at least one of the X direction and the Y direction among the following dimensional changes caused by immersion in a 2M sulfuric acid aqueous solution, Dimensional change rate caused by immersion in 2M sulfuric acid aqueous solution: A test electrolyte membrane having a water content of 1% or less was prepared, and the test electrolyte membrane was immersed in a 2M sulfuric acid aqueous solution at 25° C. for 30 minutes, and the dimensional change rate in the X direction and the Y direction orthogonal to the X direction on the surface of the test electrolyte membrane was calculated by the following formula: Dimensional change rate (%)={(dimension in a specific direction after immersion) / (dimension in a specific direction before immersion)}×100.
25. A method for manufacturing an electrolyte membrane for a redox flow battery, comprising: a step of stretching a raw material film containing a perfluorocarbon polymer having an ion exchange group under heating, and After the stretching step, a relaxation step is performed during cooling. The area stretching ratio obtained by multiplying the stretching ratio in the X-axis direction by the stretching ratio in the Y-axis direction is 2.2 to 50 times, and the relaxation rate is 0.1 to 5.0%. The perfluorocarbon polymer has an equivalent mass EW of ion exchange groups of 600 g / eq or more and 2000 g / eq or less, The crack area ratio in the electrolyte membrane is 0.1% or more and 1.5% or less, Among the following dimensional changes of the electrolyte membrane caused by immersion in distilled water, the dimensional change rate in at least one of the X direction and the Y direction is 80% or more and less than 100%, and the dimensional change rate in the Z direction is 115% or more, Dimensional change rate caused by distilled water immersion: A test electrolyte membrane having a water content of 1% or less is prepared, the test electrolyte membrane is immersed in distilled water at 25° C. for 30 minutes, and the dimensional change rates in the X direction, the Y direction orthogonal to the X direction, and the Z direction orthogonal to the X direction and the Y direction on the surface of the test electrolyte membrane are calculated. Dimensional change rate (%)={(dimension in a specific direction after immersion) / (dimension in a specific direction before immersion)}×100.
26. The method for producing an electrolyte membrane according to claim 24 or 25, wherein a raw material membrane comprising a perfluorocarbon polymer having an ion exchange group is subjected to simultaneous biaxial stretching at a temperature ranging from 20°C lower than the α dispersion temperature of the polymer to 40°C higher than the α dispersion temperature of the polymer, wherein: The α-dispersion temperature is a temperature measured by a dynamic viscoelasticity measuring device and is considered to be the temperature at which the main chain of the polymer starts thermal motion.
27. The method for manufacturing an electrolyte membrane according to claim 24 or 25, further comprising: After the relaxation treatment step, a step of heat treating the obtained film in a restrained state at a temperature not lower than the glass transition temperature and not higher than 100° C. for 1 minute to 30 minutes.
Citation Information
Patent Citations
Low density porous carbon body and production thereof
JP1992349178A
O-ring mounting method
JP2019042876A
Metallic ink
JP2019167421A
Ion-exchange fluororesin membrane
WO2002062879A1
Anode / enhanced / cathode amphoteric composite membrane for all-vanadium redox flow battery and preparation method of composite membrane
CN104282923A